A microfluidic-based PDAC organoid system reveals the impact of hypoxia in response to treatment - Geyer, Marlene; Schreyer, Daniel; Gaul, Lisa Marie; Pfeffer, Sina; Pilarsky, Christian; Queiroz, Karla (Cell Death Discovery, 2023)
Pancreatic Ductal Adenocarcinoma (PDAC) is estimated to become the second leading cause of cancer-related deaths by 2030 with mortality rates of up to 93%. Standard of care chemotherapeutic treatment only prolongs the survival of patients for a short timeframe. Therefore, it is important to understand events driving treatment failure in PDAC as well as identify potential more effective treatment opportunities. PDAC is characterized by a high-density stroma, high interstitial pressure and very low oxygen tension. The aim of this study was to establish a PDAC platform that supported the understanding of treatment response of PDAC organoids in mono-, and co-culture with pancreatic stellate cells (PSCs) under hypoxic and normoxic conditions. Cultures were exposed to Gemcitabine in combination with molecules targeting relevant molecular programs that could explain treatment specific responses under different oxygen pressure conditions. Two groups of treatment responses were identified, showing either a better effect in monoculture or co-culture. Moreover, treatment response also differed between normoxia and hypoxia. Modulation of response to Gemcitabine was also observed in presence of a Hypoxia-inducible factor (HIF) prolyl hydroxylase (PHD) inhibitor and HIF inhibitors. Altogether this highlights the importance of adjusting experimental conditions to include relevant oxygen levels in drug response studies in PDAC.
CRIS-Team Scopus Importer:2023-02-03

Ampullary Cancers Harbor ELF3 Tumor Suppressor Gene Mutations and Exhibit Frequent WNT Dysregulation - Gingras, Marie-Claude; Covington, Kyle R.; Chang, David K.; Donehower, Lawrence A.; Gill, Anthony J.; Ittmann, Michael M.; Creighton, Chad J.; Johns, Amber L.; Shinbrot, Eve; Dewal, Ninad; Fisher, William E.; Pilarsky, Christian; et al. (Cell Reports, 2016)
The ampulla of Vater is a complex cellular environment from which adenocarcinomas arise to form a group of histopathologically heterogenous tumors. To evaluate the molecular features of these tumors, 98 ampullary adenocarcinomas were evaluated and compared to 44 distal bile duct and 18 duodenal adenocarcinomas. Genomic analyses revealed mutations in the WNT signaling pathway among half of the patients and in all three adenocarcinomas irrespective of their origin and histological morphology. These tumors were characterized by a high frequency of inactivating mutations of ELF3, a high rate of microsatellite instability, and common focal deletions and amplifications, suggesting common attributes in the molecular pathogenesis are at play in these tumors. The high frequency of WNT pathway activating mutation, coupled with small-molecule inhibitors of ?-catenin in clinical trials, suggests future treatment decisions for these patients may be guided by genomic analysis.
EVALuna2:15250

Analysis of DNA Hypermethylation in Pancreatic Cancer Using Methylation-Specific PCR and Bisulfite Sequencing - Liu, Bin; Pilarsky, Christian (Methods in Molecular Biology, 2018)
Pancreatic ductal adenocarcinoma (PDAC) is an aggressive tumor and the fourth common cause of cancer death in the Western world. The lack of effective therapeutic strategies is attributed to the late diagnosis of this disease. Methylation markers could improve early detection and help in the surveillance of PDAC after treatment. Analysis of hypermethylation in the tumor tissue and tumor-derived exosomes might help to identify new therapeutic strategies and aid in the understanding of the pathophysiological changes occurring in pancreatic cancer. There are several methods for the detection of methylation events. Whereas methylation-specific PCR (MSP-PCR) is the method of choice, the cost reductions in DNA sequencing enables researchers to add bisulfite sequencing (BSS) to their repertoire if a small number of genes will be tested in a larger set of patients' samples. During the last years, several techniques to isolate and analyze DNA methylation have been proposed, but DNA modification using sodium bisulfite is still the gold standard.
CRIS-Team WoS Importer:2019-02-27

An m5C methylation regulator-associated signature predicts prognosis and therapy response in pancreatic cancer - Yun, Duo; Yang, Zhirong; Zhang, Shuman; Yang, Hai; Liu, Dongxue; Grützmann, Robert; Pilarsky, Christian; Britzen-Laurent, Nathalie (Frontiers in Cell and Developmental Biology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is the most aggressive digestive malignancy due to frequent late-stage diagnosis, rapid progression and resistance to therapy. With increasing PDAC incidence worldwide, there is an urgent need for new prognostic biomarkers and therapy targets. Recently, RNA methylation has emerged as a new tumorigenic mechanism in different cancers. 5-methylcytosine (m5C) is one of the most frequent RNA modifications and occurs on a variety of RNA species including mRNA, thereby regulating gene expression. Here we investigated the prognostic role of m5C-regulator-associated transcriptional signature in PDAC. We evaluated m5C-regulator status and expression in 239 PDAC samples from publicly available datasets. We used unsupervised consensus clustering analyses to classify PDACs based on m5C-regulator expression. From the resulting signature of differentially expressed genes (DEGs), we selected prognosis-relevant DEGs to stratify patients and build a scoring signature (m5C-score) through LASSO and multivariate Cox regression analyses. The m5C-score represented a highly significant independent prognostic marker. A high m5C-score correlated with poor prognosis in different PDAC cohorts, and was associated with the squamous/basal subtype as well as activated cancer-related pathways including Ras, MAPK and PI3K pathways. Furthermore, the m5C-score correlated with sensitivity to pathway-specific inhibitors of PARP, EGFR, AKT, HER2 and mTOR. Tumors with high m5C-score were characterized by overall immune exclusion, low CD8(+) T-cell infiltration, and higher PD-L1 expression. Overall, the m5C-score represented a robust predictor of prognosis and therapy response in PDAC, which was associated with unfavorable molecular subtypes and immune microenvironment.
CRIS-Team WoS Importer:2022-09-16

A Novel Anti-Cancer Therapy: CRISPR/Cas9 Gene Editing - Chen, Xin-Zhu; Guo, Rong; Zhao, Cong; Xu, Jing; Song, Hang; Yu, Hua; Pilarsky, Christian; Nainu, Firzan; Li, Jing-Quan; Zhou, Xin-Ke; Zhang, Jian-Ye (Frontiers in Pharmacology, 2022)
Cancer becomes one of the main causes of human deaths in the world due to the high incidence and mortality rate and produces serious economic burdens. With more and more attention is paid on cancer, its therapies are getting more of a concern. Previous research has shown that the occurrence, progression, and treatment prognosis of malignant tumors are closely related to genetic and gene mutation. CRISPR/Cas9 has emerged as a powerful method for making changes to the genome, which has extensively been applied in various cell lines. Establishing the cell and animal models by CRISPR/Cas9 laid the foundation for the clinical trials which possibly treated the tumor. CRISPR-Cas9-mediated genome editing technology brings a great promise for inhibiting migration, invasion, and even treatment of tumor. However, the potential off-target effect limits its clinical application, and the effective ethical review is necessary. The article reviews the molecular mechanisms of CRISPR/Cas9 and discusses the research and the limitation related to cancer clinical trials.
CRIS-Team WoS Importer:2022-08-12

Application of microfluidic chips in anticancer drug screening - Fan, Xin Yue; Deng, Zhuo Fen; Yan, Yan Yan; E Orel, Valerii; Shypko, Andrii; B Orel, Valerii; Ivanova, Donika; Pilarsky, Christian; Tang, Jing; Chen, Zhe Sheng; Zhang, Jian Ye (Bosnian Journal of Basic Medical Sciences, 2022)
With the continuous development of drug screening technology, new screening methodologies and technologies are constantly emerging, driving drug screening into rapid, efficient and high-throughput development. Microfluidics is a rising star in the development of innovative approaches in drug discovery. In this article, we summarize the recent years' progress of microfluidic chip technology in drug screening, including the developmental history, structural design, and applications in different aspects of microfluidic chips on drug screening. Herein, the existing microfluidic chip screening platforms are summarized from four aspects: chip structure design, sample injection and drive system, cell culture technology on a chip, and efficient remote detection technology. Furthermore, this review discusses the application and developmental prospects of using microfluidic chips in drug screening, particularly in screening natural product anticancer drugs based on chemical properties, pharmacological effects, and drug cytotoxicity.
CRIS-Team Scopus Importer:2022-06-17

Cancer is associated with alterations in the three-dimensional organization of the genome - Li, Lifei; Barth, Nicolai; Pilarsky, Christian; Taher, Leila (Cancers, 2019)
The human genome is organized into topologically associating domains (TADs), which represent contiguous regions with a higher frequency of intra-interactions as opposed to inter-interactions. TADs contribute to gene expression regulation by restricting the interactions between their regulatory elements, and TAD disruption has been associated with cancer. Here, we provide a proof of principle that mutations within TADs can be used to predict the survival of cancer patients. Specifically, we constructed a set of 1467 consensus TADs representing the three-dimensional organization of the human genome and used Cox regression analysis to identify a total of 35 prognostic TADs in different cancer types. Interestingly, only 46% of the 35 prognostic TADs comprised genes with known clinical relevance. Moreover, in the vast majority of such cases, the prognostic value of the TAD was not directly related to the presence/absence of mutations in the gene(s), emphasizing the importance of regulatory mutations. In addition, we found that 34% of the prognostic TADs show strong structural perturbations in the cancer genome, consistent with the widespread, global epigenetic dysregulation often observed in cancer patients. In summary, this study elucidates the mechanisms through which non-coding variants may influence cancer progression and opens new avenues for personalized medicine.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Biomarkers; Cancer; Copy number variants (CNVs); LASSO cox regression analysis; The cancer genome atlas (TCGA); Topologically associating domains (TADs)

CDK7 inhibition augments response to multidrug chemotherapy in pancreatic cancer - Zeng, Siyuan; Lan, Bin; Ren, Xiaofan; Zhang, Shuman; Schreyer, Daniel; Eckstein, Markus; Yang, Hai; Britzen-Laurent, Nathalie; Dahl, Andreas; Mukhopadhyay, Debabrata; Chang, David; Kutschick, Isabella; et al. (Journal of Experimental & Clinical Cancer Research, 2022)
Background: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive cancer with a dismal prognosis. Although combined treatment with gemcitabine and albumin-bound paclitaxel has improved the prognosis of PDAC, both intrinsic and acquired chemoresistance remain as severe hurtles towards improved prognosis. Thus, new therapeutic targets and innovative strategies are urgently needed. Methods: In this study, we used the KPC mouse model-derived PDAC cell line TB32047 to perform kinome-wide CRISPR-Cas9 loss-of-function screening. Next-generation sequencing and MAGeCK-VISPR analysis were performed to identify candidate genes. We then conducted cell viability, clonogenic, and apoptosis assays and evaluated the synergistic therapeutic effects of cyclin-dependent kinase 7 (CDK7) depletion or inhibition with gemcitabine (GEM) and paclitaxel (PTX) in a murine orthotopic pancreatic cancer model. For mechanistic studies, we performed genome enrichment analysis (GSEA) and Western blotting to identify and verify the pathways that render PDAC sensitive to GEM/PTX therapy. Results: We identified several cell cycle checkpoint kinases and DNA damage-related kinases as targets for overcoming chemoresistance. Among them, CDK7 ranked highly in both screenings. We demonstrated that both gene knockout and pharmacological inhibition of CDK7 by THZ1 result in cell cycle arrest, apoptosis induction, and DNA damage at least predominantly through the STAT3-MCL1-CHK1 axis. Furthermore, THZ1 synergized with GEM and PTX in vitro and in vivo, resulting in enhanced antitumor effects. Conclusions: Our findings support the application of CRISPR-Cas9 screening in identifying novel therapeutic targets and suggest new strategies for overcoming chemoresistance in pancreatic cancer.
CRIS-Team Scopus Importer:2022-08-19
Keywords: CDK7; CRISPR-Cas9; FOLFIRINOX; Gemcitabine; Paclitaxel; THZ1

Chemoresistance in Pancreatic Cancer - Zeng, Siyuan; Pöttler, Marina; Lan, Bin; Grützmann, Robert; Pilarsky, Christian; Yang, Hai (International Journal of Molecular Sciences, 2019)
Pancreatic ductal adenocarcinoma (PDAC), generally known as pancreatic cancer (PC), ranks the fourth leading cause of cancer-related deaths in the western world. While the incidence of pancreatic cancer is displaying a rising tendency every year, the mortality rate has not decreased significantly because of late diagnosis, early metastasis, and limited reaction to chemotherapy or radiotherapy. Adjuvant chemotherapy after surgical resection is typically the preferred option to treat early pancreatic cancer. Although 5-fluorouracil/leucovorin with irinotecan and oxaliplatin (FOLFIRINOX) and gemcitabine/nab-paclitaxel can profoundly improve the prognosis of advanced pancreatic cancer, the development of chemoresistance still leads to poor clinical outcomes. Chemoresistance is multifactorial as a result of the interaction among pancreatic cancer cells, cancer stem cells, and the tumor microenvironment. Nevertheless, more pancreatic cancer patients will benefit from precision treatment and targeted drugs. Therefore, we outline new perspectives for enhancing the efficacy of gemcitabine after reviewing the related factors of gemcitabine metabolism, mechanism of action, and chemoresistance.
CRIS-Team Scopus Importer:2019-09-20
Keywords: chemoresistance; FOLFIRINOX; gemcitabine; pancreatic cancer; PDAC

c-Met and PD-L1 on Circulating Exosomes as Diagnostic and Prognostic Markers for Pancreatic Cancer - Lux, Alexander; Kahlert, Christoph; Grützmann, Robert; Pilarsky, Christian (International Journal of Molecular Sciences, 2019)
Exosomes are membrane vesicles which offer potential as blood derived biomarkers for malign tumors in clinical practice. Pancreatic cancer is counted among cancer diseases with the highest mortality. The present work seeks to assess whether pancreatic carcinomas release exosomes which express c-Met (proto-oncogene mesenchymal-epithelial transition factor) and PD-L1 (programmed cell death 1 ligand 1), and whether the detection of such expression in serum has diagnostic or prognostic meaning for the affected patients. Exosome isolation was performed on culture media of one benign pancreatic cell line and ten pancreatic carcinoma cell lines as well as on serum samples from 55 patients with pancreatic ductal adenocarcinoma (PDAC), 26 patients with chronic pancreatitis and 10 patients with benign serous cyst adenoma of the pancreas. Exosomes were bound to latex beads and stained with antibodies against c-Met or PD-L1. Analysis of fluorescence intensity was performed by flow cytometry. In terms of c-Met, the mean fluorescence intensity of PDAC-patients was significantly higher than the fluorescence intensity of the comparative patients with benign disease (p < 0.001). A diagnostic test based on c-Met resulted in a sensitivity of 70%, a specificity of 85% and a diagnostic odds ratio of 13:2. The specificity of the test can be further improved by combining it with the established tumor marker carbohydrate antigen 19-9 (CA 19-9). In addition, c-Met-positive patients showed a significantly shorter postoperative survival time (9.5 vs. 21.7 months, p < 0.001). In terms of PD-L1, no significant difference between fluorescence intensity of PDAC-patients and comparative patients was detectable. However, PD-L1-positive PDAC-patients also showed a significantly shorter postoperative survival time (7.8 vs. 17.2 months, p = 0.043). Thus, both markers can be considered as negative prognostic factors.
CRIS-Team Scopus Importer:2019-07-30
Keywords: c-Met; chronic pancreatitis; exosomes; pancreatic cancer; PD-L1; PDAC; serous cyst adenoma

CRISPR Cas9 in Pancreatic Cancer Research - Yang, Hai; Bailey, Peter; Pilarsky, Christian (Frontiers in Cell and Developmental Biology, 2019)
Pancreatic cancer is now becoming a common cause of cancer death with no significant change in patient survival over the last 10 years. The main treatment options for pancreatic cancer patients are surgery, radiation therapy and chemotherapy, but there is now considerable effort to develop new and effective treatments. In recent years, CRISPR/Cas9 technology has emerged as a powerful gene editing tool with promise, not only as an important research methodology, but also as a new and effective method for targeted therapy. In this review, we summarize current advances in CRISPR/Cas9 technology and its application to pancreatic cancer research, and importantly as a means of selectively targeting key drivers of pancreatic cancer.
CRIS-Team Scopus Importer:2019-11-15
Keywords: CRISPR/Cas9; gene editing; knock out and knock in; library screening; pancreatic cancer

CRISPR/Cas9-mediated knock-out of krasG12D mutated pancreatic cancer cell lines - Lentsch, Eva; Li, Lifei; Pfeffer, Sina; Ekici, Arif Bülent; Taher, Leila; Pilarsky, Christian; Grützmann, Robert (International Journal of Molecular Sciences, 2019)
In 90% of pancreatic ductal adenocarcinoma cases, genetic alteration of the proto-oncogene Kras has occurred, leading to uncontrolled proliferation of cancerous cells. Targeting Kras has proven to be difficult and the battle against pancreatic cancer is ongoing. A promising approach to combat cancer was the discovery of the clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated (Cas) system, which can be used to genetically modify cells. To assess the potential of a CRISPR/CRISPR-associated protein 9 (Cas9) method to eliminate Kras mutations in cells, we aimed to knock-out the c.35G>A (p.G12D) Kras mutation. Therefore, three cell lines with a heterozygous Kras mutation (the human cell lines SUIT-2 and Panc-1 and the cell line TB32047 from a KPC mouse model) were used. After transfection, puromycin selection and single-cell cloning, proteins from two negative controls and five to seven clones were isolated to verify the knock-out and to analyze changes in key signal transduction proteins. Western blots showed a specific knock-out in the KrasG12D protein, but wildtype Kras was expressed by all of the cells. Signal transduction analysis (for Erk, Akt, Stat3, AMPKα, and c-myc) revealed expression levels similar to the wildtype. The results described herein indicate that knocking-out the KrasG12D mutation by CRISPR/Cas9 is possible. Additionally, under regular growth conditions, the knock-out clones resembled wildtype cells.
CRIS-Team Scopus Importer:2019-11-26
Keywords: CRISPR/Cas9 system; G12D; Kras; Panc-1; Suit-2; TB32047

CRISPR-Cas9 Screen Identifies DYRK1A as a Target for Radiotherapy Sensitization in Pancreatic Cancer - Lan, Bin; Zeng, Siyuan; Zhang, Shuman; Ren, Xiaofan; Xing, Yuming; Kutschick, Isabella; Pfeffer, Sina; Frey, Benjamin; Britzen-Laurent, Nathalie; Grützmann, Robert; Cordes, Nils; Pilarsky, Christian (Cancers, 2022)
Although radiation therapy has recently made great advances in cancer treatment, the majority of patients diagnosed with pancreatic cancer (PC) cannot achieve satisfactory outcomes due to intrinsic and acquired radioresistance. Identifying the molecular mechanisms that impair the efficacy of radiotherapy and targeting these pathways are essential to improve the radiation response of PC patients. Our goal is to identify sensitive targets for pancreatic cancer radiotherapy (RT) using the kinome-wide CRISPR-Cas9 loss-of-function screen and enhance the therapeutic effect through the development and application of targeted inhibitors combined with radiotherapy. We transduced pancreatic cancer cells with a protein kinase library; 2D and 3D library cells were irradiated daily with a single dose of up to 2 Gy for 4 weeks for a total of 40 Gy using an X-ray generator. Sufficient DNA was collected for next-generation deep sequencing to identify candidate genes. In this study, we identified several cell cycle checkpoint kinases and DNA damage related kinases in 2D-and 3D-cultivated cells, including DYRK1A, whose loss of function sensitizes cells to radiotherapy. Additionally, we demonstrated that the harmine-targeted suppression of DYRK1A used in conjunction with radiotherapy increases DNA double-strand breaks (DSBs) and impairs homologous repair (HR), resulting in more cancer cell death. Our results support the use of CRISPR-Cas9 screening to identify new therapeutic targets, develop radiosensitizers, and provide novel strategies for overcoming the tolerance of pancreatic cancer to radiotherapy.
CRIS-Team Scopus Importer:2022-01-14
Keywords: CRISPR-Cas9; DNA damage repair; DNA double-strand break; DYRK1A; Harmine; Pancreatic cancer; Radioresistance; Radiotherapy

Current Clinical Strategies of Pancreatic Cancer Treatment and Open Molecular Questions - Brunner, Maximilian; Wu, Zhiyuan; Krautz, Christian; Pilarsky, Christian; Grützmann, Robert; Weber, Georg (International Journal of Molecular Sciences, 2019)
Pancreatic cancer is one of the most lethal malignancies and is associated with a poor prognosis. Surgery is considered the only potential curative treatment for pancreatic cancer, followed by adjuvant chemotherapy, but surgery is reserved for the minority of patients with non-metastatic resectable tumors. In the future, neoadjuvant treatment strategies based on molecular testing of tumor biopsies may increase the amount of patients becoming eligible for surgery. In the context of non-metastatic disease, patients with resectable or borderline resectable pancreatic carcinoma might benefit from neoadjuvant chemo- or chemoradiotherapy followed by surgeryPatients with locally advanced or (oligo-/poly-)metastatic tumors presenting significant response to (neoadjuvant) chemotherapy should undergo surgery if R0 resection seems to be achievable. New immunotherapeutic strategies to induce potent immune response to the tumors and investigation in molecular mechanisms driving tumorigenesis of pancreatic cancer may provide novel therapeutic opportunities in patients with pancreatic carcinoma and help patient selection for optimal treatment.
CRIS-Team Scopus Importer:2019-10-01
Keywords: chemoradiation; chemotherapy; immunotherapy; molecular mechanism; pancreatic cancer; surgery; therapeutic targets; treatment options

Cytosolic 5 '-nucleotidase 1A is overexpressed in pancreatic cancer and mediates gemcitabine resistance by reducing intracellular gemcitabine metabolites - Patzak, Melanie S.; Kari, Vijayalakshmi; Patil, Shilpa; Hamdan, Feda H.; Goetze, Robert G.; Brunner, Marius; Gaedcke, Jochen; Kitz, Julia; Jodrell, Duncan; Richards, Frances M.; Pilarsky, Christian; Grützmann, Robert; et al. (EBioMedicine, 2019)
Background: Cytosolic 5'-nucleotidase 1A (NT5C1A) dephosphorylates non-cyclic nucleoside monophosphates to produce nucleosides and inorganic phosphates. Here, we investigate NT5C1A expression in pancreatic ductal adenocarcinoma (PDAC) and its impact on gemcitabine metabolism and therapeutic efficacy.
CRIS-Team WoS Importer:2019-03-22

Deep learning improves pancreatic cancer diagnosis using rna-based variants - Al-Fatlawi, Ali; Malekian, Negin; García, Sebastián; Henschel, Andreas; Kim, Ilwook; Dahl, Andreas; Jahnke, Beatrix; Bailey, Peter; Bolz, Sarah Naomi; Poetsch, Anna R.; Mahler, Sandra; Grützmann, Robert; et al. (Cancers, 2021)
For optimal pancreatic cancer treatment, early and accurate diagnosis is vital. Blood-derived biomarkers and genetic predispositions can contribute to early diagnosis, but they often have limited accuracy or applicability. Here, we seek to exploit the synergy between them by combining the biomarker CA19-9 with RNA-based variants. We use deep sequencing and deep learning to improve differentiating pancreatic cancer and chronic pancreatitis. We obtained samples of nucleated cells found in peripheral blood from 268 patients suffering from resectable, non-resectable pancreatic cancer, and chronic pancreatitis. We sequenced RNA with high coverage and obtained millions of variants. The high-quality variants served as input together with CA19-9 values to deep learning models. Our model achieved an area under the curve (AUC) of 96% in differentiating resectable cancer from pancreatitis using a test cohort. Moreover, we identified variants to estimate survival in resectable cancer. We show that the blood transcriptome harbours variants, which can substantially improve noninvasive clinical diagnosis.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Chronic pancreatitis; Deep learning; Pancreatic cancer; Transcriptome-wide association study

Detection of COPB2 as a KRAS synthetic lethal partner through integration of functional genomics screens - Christodoulou, Eleni G.; Yang, Hai; Lademann, Franziska; Pilarsky, Christian; Beyer, Andreas; Schroeder, Michael (Oncotarget, 2017)
Mutated KRAS plays an important role in many cancers. Although targeting KRAS directly is difficult, indirect inactivation via synthetic lethal partners (SLPs) is promising. Yet to date, there are no SLPs from high-throughput RNAi screening, which are supported by multiple screens. Here, we address this problem by aggregating and ranking data over three independent high-throughput screens. We integrate rankings by minimizing the displacement and by considering established methods such as RIGER and RSA.Our meta analysis reveals COPB2 as a potential SLP of KRAS with good support from all three screens. COPB2 is a coatomer subunit and its knock down has already been linked to disabled autophagy and reduced tumor growth. We confirm COPB2 as SLP in knock down experiments on pancreas and colorectal cancer cell lines.Overall, consistent integration of high throughput data can generate candidate synthetic lethal partners, which individual screens do not uncover. Concretely, we reveal and confirm that COPB2 is a synthetic lethal partner of KRAS and hence a promising cancer target. Ligands inhibiting COPB2 may, therefore, be promising new cancer drugs.
EVALuna2:15311

Development and Validation of a Multivariable Prediction Model Based on Blood Plasma and Serum Metabolomics for the Diagnosis of Chronic Pancreatitis - Beyer, G.; Adam, M. G.; Christiansen, N.; Kamlage, B.; Pilarsky, Christian; Distler, M.; Falbusch, T.; Chromik, A.; Klein, F.; Bahra, M.; Uhl, W.; Grützmann, Robert; et al. (PANCREAS, 2020)
CRIS-Team WoS Importer:2021-02-19

Development of a Class Prediction Model to Discriminate Pancreatic Ductal Adenocarcinoma from Pancreatic Neuroendocrine Tumor by MALDI Mass Spectrometry Imaging - Casadonte, Rita; Kriegsmann, Mark; Perren, Aurel; Baretton, Gustavo; Deininger, Soeren-Oliver; Kriegsmann, Katharina; Welsch, Thilo; Pilarsky, Christian; Kriegsmann, Joerg (Proteomics Clinical Applications, 2019)
Purpose To define proteomic differences between pancreatic ductal adenocarcinoma (pDAC) and pancreatic neuroendocrine tumor (pNET) by matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI MSI). Experimental design Ninety-three pDAC and 126 pNET individual tissues are assembled in tissue microarrays and analyzed by MALDI MSI. The cohort is separated in a training (52 pDAC and 83 pNET) and validation set (41 pDAC and 43 pNET). Subsequently, a linear discriminant analysis (LDA) model based on 46 peptide ions is performed on the training set and evaluated on the validation cohort. Additionally, two liver metastases and a whole slide of pDAC are analyzed by the same LDA algorithm. Results Classification of pDAC and pNET by the LDA model is correct in 95% (39/41) and 100% (43/43) of patients in the validation cohort, respectively. The two liver metastases and the whole slide of pDAC are also correctly classified in agreement with the histopathological diagnosis. Conclusion and clinical relevance: In the present study, a large dataset of pDAC and pNET by MALDI MSI is investigated, a class prediction model that allowed separation of both entities with high accuracy is developed, and differential peptide peaks with potential diagnostic, prognostic, and predictive values are highlighted.
CRIS-Team WoS Importer:2019-02-27

Expression and role of the immune checkpoint regulator PD-L1 in the tumor-stroma interplay of pancreatic ductal adenocarcinoma - Daunke, Tina; Beckinger, Silje; Rahn, Sascha; Krüger, Sandra; Heckl, Steffen; Schäfer, Heiner; Wesch, Daniela; Pilarsky, Christian; Eckstein, Markus; Hartmann, Arndt; Röcken, Christoph; Wandmacher, Anna Maxi; et al. (Frontiers in Immunology, 2023)
Introduction: Immune checkpoint inhibitors (ICI), e.g., targeting programmed cell death protein 1-ligand 1 (PD-L1) or its receptor PD-1, have markedly improved the therapy of many cancers but so far failed in pancreatic ductal adenocarcinoma (PDAC). Macrophages represent one of the most abundant immune cell populations within the tumor microenvironment (TME) of PDAC being able to either support or restrain tumor progression depending on their phenotype. To better understand treatment failure of PD-L1/PD-1 inhibitors in PDAC, this study examined PD-L1 expression in the context of a dynamic TME in PDAC with a particular focus on the impact of macrophages. Methods: Formalin-fixed and paraffin embedded tissue samples of primary PDAC tissues and corresponding liver metastases were used for immunohistochemical analyses. Serial sections were stained with antibodies detecting Pan-Cytokeratin, CD68, CD163, CD8, and PD-L1.To investigate whether the PD-1/PD-L1 axis and macrophages contribute to immune escape of PDAC cells, a stroma enriched 3D spheroid coculture model was established in vitro, using different PDAC cell lines and macrophages subtypes as well as CD8+ T cells. Functional and flow cytometry analyses were conducted to characterize cell populations. Results: Immunohistochemical analyses revealed that PD-L1 is mainly expressed by stroma cells, including macrophages and not PDAC cells in primary PDAC tissues and corresponding liver metastases. Notably, high local abundance of macrophages and strong PD-L1 staining were commonly found at invasion fronts of tumoral lesions between CD8+ T cells and tumor cells. In order to investigate whether PD-L1 expressing macrophages impact the response of PDAC cells to treatment with PD-L1/PD-1 inhibitors, we developed a spheroid model comprising two different PDAC cell lines and different ratios of in vitro differentiated primary M1- or M2-like polarized macrophages. In line with our in situ findings, high PD-L1 expression was observed in macrophages rather than PDAC cells, which was further increased by the presence of PDAC cells. The effector phenotype of co-cultured CD8+ T cells exemplified by expression of activation markers and release of effector molecules was rather enhanced by PDAC macrophage spheroids, particularly with M1-like macrophages compared to mono-culture spheroids. However, this was not associated with enhanced PDAC cell death. ICI treatment with either Durvalumab or Pembrolizumab alone or in combination with Gemcitabine hardly affected the effector phenotype of CD8+ T cells along with PDAC cell death. Thus, despite strong PD-L1 expression in macrophages, ICI treatment did not result in an enhanced activation and cytotoxic phenotype of CD8+ T cells. Conclusion: Overall, our study revealed novel insights into the interplay of PDAC cells and macrophages in the presence of ICI.
CRIS-Team Scopus Importer:2023-08-25
Keywords: 3D co-culture; immune checkpoint inhibitor; immune evasion; macrophages; pancreatic cancer; tumor microenvironment

GATA4 and GATA6 loss-of-expression is associated with extinction of the classical programme and poor outcome in pancreatic ductal adenocarcinoma - De Andres, Monica P.; Jackson, Richard J.; Felipe, Irene; Zagorac, Sladjana; Pilarsky, Christian; Schlitter, Anna Melissa; Martinez De Villareal, Jaime; Jang, Gun Ho; Costello, Eithne; Gallinger, Steve; Ghaneh, Paula; Greenhalf, William; et al. (Gut, 2022)
Objective GATA6 is a key regulator of the classical phenotype in pancreatic ductal adenocarcinoma (PDAC). Low GATA6 expression associates with poor patient outcome. GATA4 is the second most expressed GATA factor in the pancreas. We assessed whether, and how, GATA4 contributes to PDAC phenotype and analysed the association of expression with outcome and response to chemotherapy. Design We analysed PDAC transcriptomic data, stratifying cases according to GATA4 and GATA6 expression and identified differentially expressed genes and pathways. The genome-wide distribution of GATA4 was assessed, as well as the effects of GATA4 knockdown. A multicentre tissue microarray study to assess GATA4 and GATA6 expression in samples (n=745) from patients with resectable was performed. GATA4 and GATA6 levels were dichotomised into high/low categorical variables; association with outcome was assessed using univariable and multivariable Cox regression models. Results GATA4 messenger RNA is enriched in classical, compared with basal-like tumours. We classified samples in 4 groups as high/low for GATA4 and GATA6. Reduced expression of GATA4 had a minor transcriptional impact but low expression of GATA4 enhanced the effects of GATA6 low expression. GATA4 and GATA6 display a partially overlapping genome-wide distribution, mainly at promoters. Reduced expression of both proteins in tumours was associated with the worst patient survival. GATA4 and GATA6 expression significantly decreased in metastases and negatively correlated with basal markers. Conclusions GATA4 and GATA6 cooperate to maintain the classical phenotype. Our findings provide compelling rationale to assess their expression as biomarkers of poor prognosis and therapeutic response.
CRIS-Team WoS Importer:2022-09-30

Genome-Wide CRISPR Screening Identifies DCK and CCNL1 as Genes That Contribute to Gemcitabine Resistance in Pancreatic Cancer - Yang, Hai; Liu, Bin; Liu, Dongxue; Yang, Zhirong; Zhang, Shuman; Xu, Pengyan; Xing, Yuming; Kutschick, Isabella; Pfeffer, Sina; Britzen-Laurent, Nathalie; Grützmann, Robert; Pilarsky, Christian (Cancers, 2022)
Pancreatic cancer is one of the most lethal cancers. Due to the difficulty of early diagnosis, most patients are diagnosed with metastasis or advanced-stage cancer, limiting the possibility of surgical treatment. Therefore, chemotherapy is applied to improve patient outcomes, and gemcitabine has been the primary chemotherapy drug for pancreatic cancer for over a decade. However, drug resistance poses a significant challenge to the efficacy of chemotherapy. The CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9) gene-editing system is a powerful tool, and researchers have developed CRISPR/Cas9 library screening as a means to identify the genes associated with specific phenotype changes. We performed genomewide CRISPR/Cas9 knockout screening in the mouse pancreatic cancer cell line TB32047 with gemcitabine treatment and identified deoxycytidine kinase (DCK) and cyclin L1 (CCNL1) as the top hits. We knocked out DCK and CCNL1 in the TB32047 and PANC1 cell lines and confirmed that the loss of DCK or CCNL1 enhanced gemcitabine resistance in pancreatic cells. Many researchers have addressed the mechanism of DCK-related gemcitabine resistance; however, no study has focused on CCNL1 and gemcitabine resistance. Therefore, we explored the mechanism of CCNL1-related gemcitabine resistance and found that the loss of CCNL1 activates the ERK/AKT/STAT3 survival pathway, causing cell resistance to gemcitabine treatment.
CRIS-Team Scopus Importer:2022-07-15
Keywords: CCNL1; CRISPR-Cas9; DCK; gemcitabine resistance; library screening; pancreatic cancer

Genomic analyses identify molecular subtypes of pancreatic cancer - Bailey, Peter; Chang, David K.; Nones, Katia; Johns, Amber L.; Patch, Ann-Marie; Gingras, Marie-Claude; Miller, David K.; Christ, Angelika N.; Bruxner, Tim J. C.; Quinn, Michael C.; Nourse, Craig; Murtaugh, L. Charles; et al. (Nature, 2016)
Integrated genomic analysis of 456 pancreatic ductal adenocarcinomas identified 32 recurrently mutated genes that aggregate into 10 pathways: KRAS, TGF-?, WNT, NOTCH, ROBO/SLIT signalling, G1/S transition, SWI-SNF, chromatin modification, DNA repair and RNA processing. Expression analysis defined 4 subtypes: (1) squamous; (2) pancreatic progenitor; (3) immunogenic; and (4) aberrantly differentiated endocrine exocrine (ADEX) that correlate with histopathological characteristics. Squamous tumours are enriched for TP53 and KDM6A mutations, upregulation of the TP63?N transcriptional network, hypermethylation of pancreatic endodermal cell-fate determining genes and have a poor prognosis. Pancreatic progenitor tumours preferentially express genes involved in early pancreatic development (FOXA2/3, PDX1 and MNX1). ADEX tumours displayed upregulation of genes that regulate networks involved in KRAS activation, exocrine (NR5A2 and RBPJL), and endocrine differentiation (NEUROD1 and NKX2-2). Immunogenic tumours contained upregulated immune networks including pathways involved in acquired immune suppression. These data infer differences in the molecular evolution of pancreatic cancer subtypes and identify opportunities for therapeutic development.
EVALuna2:15255

HNF4A and GATA6 Loss Reveals Therapeutically Actionable Subtypes in Pancreatic Cancer - Brunton, Holly; Caligiuri, Giuseppina; Cunningham, Richard; Upstill-Goddard, Rosie; Bailey, Ulla Maja; Garner, Ian M.; Nourse, Craig; Dreyer, Stephan; Jones, Marc; Moran-Jones, Kim; Wright, Derek W.; Paulus-Hock, Viola; et al. (Cell Reports, 2020)
Pancreatic ductal adenocarcinoma (PDAC) can be divided into transcriptomic subtypes with two broad lineages referred to as classical (pancreatic) and squamous. We find that these two subtypes are driven by distinct metabolic phenotypes. Loss of genes that drive endodermal lineage specification, HNF4A and GATA6, switch metabolic profiles from classical (pancreatic) to predominantly squamous, with glycogen synthase kinase 3 beta (GSK3β) a key regulator of glycolysis. Pharmacological inhibition of GSK3β results in selective sensitivity in the squamous subtype; however, a subset of these squamous patient-derived cell lines (PDCLs) acquires rapid drug tolerance. Using chromatin accessibility maps, we demonstrate that the squamous subtype can be further classified using chromatin accessibility to predict responsiveness and tolerance to GSK3β inhibitors. Our findings demonstrate that distinct patterns of chromatin accessibility can be used to identify patient subgroups that are indistinguishable by gene expression profiles, highlighting the utility of chromatin-based biomarkers for patient selection in the treatment of PDAC. Brunton et al. demonstrate that differential chromatin accessibility can predict responsiveness and tolerance to GSK3β inhibitors in the squamous subtype of PDAC. This study provides an important proof of concept that chromatin accessibility can be used to identify additional PDAC subgroups with potential therapeutic utility.
CRIS-Team Scopus Importer:2020-05-19
Keywords: chromatin landscapes; GATA6; GSK3B; HNF4A; intronic and distal promoters; metabolic targeting; PDAC subtypes; therapeutic tolerance

Hypermutation In Pancreatic Cancer - Humphris, Jeremy L.; Patch, Ann-Marie; Nones, Katia; Bailey, Peter J.; Johns, Amber L.; Mckay, Skye; Chang, David K.; Miller, David K.; Pajic, Marina; Kassahn, Karin S.; Quinn, Michael C. J.; Bruxner, Timothy J. C.; et al. (Gastroenterology, 2017)
Pancreatic cancer is molecularly diverse, with few effective therapies. Increased mutation burden and defective DNA repair are associated with response to immune checkpoint inhibitors in several other cancer types. We interrogated 385 pancreatic cancer genomes to define hypermutation and its causes. Mutational signatures inferring defects in DNA repair were enriched in those with the highest mutation burdens. Mismatch repair deficiency was identified in 1% of tumors harboring different mechanisms of somatic inactivation of MLH1 and MSH2. Defining mutation load in individual pancreatic cancers and the optimal assay for patient selection may inform clinical trial design for immunotherapy in pancreatic cancer.
EVALuna2:15259

Identification and validation of a multivariable prediction model based on blood plasma and serum metabolomics for the distinction of chronic pancreatitis subjects from non-pancreas disease control subjects - Adam, M. Gordian; Beyer, Georg; Christiansen, Nicole; Kamlage, Beate; Pilarsky, Christian; Distler, Marius; Fahlbusch, Tim; Chromik, Ansgar; Klein, Fritz; Bahra, Marcus; Uhl, Waldemar; Grützmann, Robert; et al. (Gut, 2021)
Objective Chronic pancreatitis (CP) is a fibroinflammatory syndrome leading to organ dysfunction, chronic pain, an increased risk for pancreatic cancer and considerable morbidity. Due to a lack of specific biomarkers, diagnosis is based on symptoms and specific but insensitive imaging features, preventing an early diagnosis and appropriate management. Design We conducted a type 3 study for multivariable prediction for individual prognosis according to the TRIPOD guidelines. A signature to distinguish CP from controls (n=160) was identified using gas chromatography-mass spectrometry and liquid chromatography-tandem mass spectrometry on ethylenediaminetetraacetic acid (EDTA)-plasma and validated in independent cohorts. Results A Naive Bayes algorithm identified eight metabolites of six ontology classes. After algorithm training and computation of optimal cut-offs, classification according to the metabolic signature detected CP with an area under the curve (AUC) of 0.85 ((95% CI 0.79 to 0.91). External validation in two independent cohorts (total n=502) resulted in similar accuracy for detection of CP compared with non-pancreatic controls in EDTA-plasma (AUC 0.85 (95% CI 0.81 to 0.89)) and serum (AUC 0.87 (95% CI 0.81 to 0.95)). Conclusions This is the first study that identifies and independently validates a metabolomic signature in plasma and serum for the diagnosis of CP in large, prospective cohorts. The results could provide the basis for the development of the first routine laboratory test for CP.
CRIS-Team WoS Importer:2021-11-05

Identification of Genes Associated with Liver Metastasis in Pancreatic Cancer Reveals PCSK6 as a Crucial Mediator - He, Hang; Zhang, Shuman; Yang, Hai; Xu, Pengyan; Kutschick, Isabella; Pfeffer, Sina; Britzen-Laurent, Nathalie; Grützmann, Robert; Fu, Deliang; Pilarsky, Christian (Cancers, 2023)
Liver metastasis occurs frequently in patients with pancreatic cancer. We analyzed the molecular profiling in liver metastatic lesions aiming to uncover novel genes responsible for tumor progression. Bioinformatics analysis was applied to identify genes directing liver metastasis. CRISPR/Cas9 technology was used to knock out the candidate gene. Proliferation assays, colony formation assays, cell cycle analysis, migration assays, wound healing assays, Immunofluorescence analysis, and the tumor xenograft model of intrasplenic injection were adopted to evaluate the effects of PCSK6 inactivation on cell growth, migration and liver metastasis. GSEA and Western blot were used to investigate the corresponding signaling pathway. PCSK6 was one of the obtained liver-metastasis-related genes in pancreatic cancer. PCSK6 inactivation inhibited cell growth and cell migration, due to G0/G1 cell cycle arrest and the remodeling of cell–cell junctions or the cell skeleton, respectively. PCSK6 inactivation led to fewer counts and lower outgrowth rates of liver metastatic niches in vivo. The Raf-MEK1/2-ERK1/2 axis was repressed by PCSK6 inactivation. Accordingly, we found PCSK6 inactivation could inhibit cell growth, cell migration, and liver metastasis, and explored the role of the Raf-MEK1/2-ERK1/2 axis in PCSK6 inactivation. PCSK6-targeted therapy might represent a novel approach for combatting liver metastasis in pancreatic cancer.
CRIS-Team Scopus Importer:2023-01-20
Keywords: CRISPR/Cas9; ERK; liver metastasis; PCSK6

IL-3: key orchestrator of inflammation - Podolska, Malgorzata; Grützmann, Robert; Pilarsky, Christian; Benard, Alan (Frontiers in Immunology, 2024)
Interleukin (IL)-3 has long been known for its hematopoietic properties. However, recent evidence has expanded our understanding of IL-3 function by identifying IL-3 as a critical orchestrator of inflammation in a wide array of diseases. Depending on the type of disease, the course of inflammation, the cell or the tissue involved, IL-3 promotes either pathologic inflammation or its resolution. Here, we describe the cell-specific functions of IL-3 and summarize its role in diseases. We discuss the current treatments targeting IL-3 or its receptor, and highlight the potential and the limitations of targeting IL-3 in clinics.
CRIS-Team Scopus Importer:2024-07-12
Keywords: cancer; CD123; infection; inflammation; interleukin-3

Impact of CRISPR/Cas9-Mediated CD73 Knockout in Pancreatic Cancer - Zhang, Jinping; Zhang, Shuman; Dörflein, Isabella; Ren, Xiaofan; Pfeffer, Sina; Britzen-Laurent, Nathalie; Grützmann, Robert; Duan, Xianglong; Pilarsky, Christian (Cancers, 2023)
Pancreatic cancer is among the cancers with the highest mortality rates. Most of the patients are found to have advanced cancer, losing the chance of surgical treatment, and there is an urgent need to find new treatment methods. Targeted therapy for specific genes that play a key role in cancer is now an important means to improve the survival rate of patients. We determined that CD73 is highly expressed in pancreatic cancer by flow cytometry and qRT-PCR assays combined with bioinformatics techniques. Application of CRISPR/Cas9 technology to knockout CD73 in human and murine cell lines, respectively, revealed that CD73 inactivation inhibited cell growth and migration and induced G1 cell cycle arrest. We also found that CD73 deletion inhibited the ERK/STAT3 pathway and activated the E-cadherin pathway. In addition, a CRISPR/Cas9 protein kinase library screen was performed and identified Pbk, Fastk, Cdk19, Adck5, Trim28, and Pfkp as possible genes regulating CD73.
CRIS-Team Scopus Importer:2023-10-20
Keywords: CD73; CRISPR/Cas9; deep sequencing; pancreatic cancer

Independent Validation and Assay Standardization of Improved Metabolic Biomarker Signature to Differentiate Pancreatic Ductal Adenocarcinoma From Chronic Pancreatitis - Mahajan, Ujjwal M.; Oehrle, Bettina; Sirtl, Simon; Alnatsha, Ahmed; Goni, Elisabetta; Regel, Ivonne; Beyer, Georg; Vornhülz, Marlies; Vielhauer, Jakob; Chromik, Ansgar; Bahra, Markus; Klein, Fritz; et al. (Gastroenterology, 2022)
Background & Aims: Pancreatic ductal adenocarcinoma cancer (PDAC) is a highly lethal malignancy requiring efficient detection when the primary tumor is still resectable. We previously developed the MxPancreasScore comprising 9 analytes and serum carbohydrate antigen 19-9 (CA19-9), achieving an accuracy of 90.6%. The necessity for 5 different analytical platforms and multiple analytical runs, however, hindered clinical applicability. We therefore aimed to develop a simpler single-analytical run, single-platform diagnostic signature. Methods: We evaluated 941 patients (PDAC, 356; chronic pancreatitis [CP], 304; nonpancreatic disease, 281) in 3 multicenter independent tests, and identification (ID) and validation cohort 1 (VD1) and 2 (VD2) were evaluated. Targeted quantitative plasma metabolite analysis was performed on a liquid chromatography–tandem mass spectrometry platform. A machine learning–aided algorithm identified an improved (i-Metabolic) and minimalistic metabolic (m-Metabolic) signatures, and compared them for performance. Results: The i-Metabolic Signature, (12 analytes plus CA19-9) distinguished PDAC from CP with area under the curve (95% confidence interval) of 97.2% (97.1%-97.3%), 93.5% (93.4%-93.7%), and 92.2% (92.1%-92.3%) in the ID, VD1, and VD2 cohorts, respectively. In the VD2 cohort, the m-Metabolic signature (4 analytes plus CA19-9) discriminated PDAC from CP with a sensitivity of 77.3% and specificity of 89.6%, with an overall accuracy of 82.4%. For the subset of 45 patients with PDAC with resectable stages IA-IIB tumors, the sensitivity, specificity, and accuracy were 73.2%, 89.6%, and 82.7%, respectively; for those with detectable CA19-9 >2 U/mL, 81.6%, 88.7%, and 84.5%, respectively; and for those with CA19-9 <37 U/mL, 39.7%, 94.1%, and 76.3%, respectively. Conclusions: The single-platform, single-run, m-Metabolic signature of just 4 metabolites used in combination with serum CA19-9 levels is an innovative accurate diagnostic tool for PDAC at the time of clinical presentation, warranting further large-scale evaluation.
CRIS-Team Scopus Importer:2022-11-04
Keywords: CA19-9; Chronic Pancreatitis; Diagnostic Signature; Metabolic Signature; Pancreatic Cancer

Influence of body mass index on long-term outcome in patients with rectal cancer-a single centre experience - Kalb, Maximilian; Langheinrich, Melanie C.; Merkel, Susanne; Krautz, Christian; Brunner, Maximilian; Bénard, Alan; Weber, Klaus; Pilarsky, Christian; Grützmann, Robert; Weber, Georg (Cancers, 2019)
Background: Excess bodyweight is known to influence the risk of colorectal cancer; however, little evidence exists for the influence of the body mass index (BMI) on the long-term outcome of patients with rectal cancer. Methods: We assessed the impact of the BMI on the risk of local recurrence, distant metastasis and overall-survival in 612 patients between 2003 and 2010 after rectal cancer diagnosis and treatment at the University Hospital Erlangen. A Cox-regression model was used to estimate the hazard ratio and multivariate risk of mortality and distant-metastasis. Median follow up-time was 58 months. Results: Patients with obesity class II or higher (BMI ≥ 35 kg/m2, n = 25) and patients with underweight (BMI < 18.5 kg/m2, n = 5) had reduced overall survival (hazard ratio (HR) = 1.6; 95% confidence interval (CI) 0.9-2.7) as well as higher rates of distant metastases (hazard ratio HR = 1.7; 95% CI 0.9-3.3) as compared to patients with normal bodyweight (18.5 ≤ BMI < 25 kg/m2, n = 209), overweight (25 ≤ BMI <30 kg/m2, n = 257) or obesity class I (30 ≤ BMI >35 kg/m2, n = 102). There were no significant differences for local recurrence. Conclusions: Underweight and excess bodyweight are associated with lower overall survival and higher rates of distant metastasis in patients with rectal cancer.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Body mass index; Distant metastasis; Overall survival; Rectal cancer

In silico analysis of the transportome in human pancreatic ductal adenocarcinoma - Zaccagnino, A.; Pilarsky, Christian; Tawfik, D.; Sebens, Susanne; Trauzold, A.; Novak, Ivana; Schwab, A.; Kalthoff, H. (European Biophysics Journal, 2016)
The altered expression and/or activity of ion channels and transporters (transportome) have been associated with malignant behavior of cancer cells and were proposed to be a hallmark of cancer. However, the impact of altered transportome in epithelial cancers, such as pancreatic ductal adenocarcinoma (PDAC), as well as its pathophysiological consequences, still remains unclear. Here, we report the in silico analysis of 840 transportome genes in PDAC patients' tissues. Our study was focused on the transportome changes and their correlation with functional and behavioral responses in PDAC tumor and stromal compartments. The dysregulated gene expression datasets were filtered using a cut-off of fold-change values <=-2 or >=2 (adjusted p value <=0.05). The dysregulated transportome genes were clearly associated with impaired physiological secretory mechanisms and/or pH regulation, control of cell volume, and cell polarity. Additionally, some down-regulated transportome genes were found to be closely linked to epithelial cell differentiation. Furthermore, the observed decrease in genes coding for calcium and chloride transport might be a mechanism for evasion of apoptosis. In conclusion, the current work provides a comprehensive overview of the altered transportome expression and its association with predicted PDAC malignancy with special focus on the epithelial compartment.
EVALuna2:15285

Intracellular Quantification and Localization of Label-Free Iron Oxide Nanoparticles by Holotomographic Microscopy - Friedrich, Ralf P.; Schreiber, Eveline; Tietze, Rainer; Yang, Hai; Pilarsky, Christian; Alexiou, Christoph (Nanotechnology, Science and Applications, 2020)
Background: The limitations of optical microscopy to determine the cellular localization of label-free nanoparticles prevent a solid prediction of the cellular effect of particles intended for medical applications. To avoid the strong physicochemical changes associated with fluorescent labelling, which often result in differences in cellular uptake, efficiency and toxicity of particles, novel detection techniques are required.
CRIS-Team WoS Importer:2021-01-29

Loss of IFN-gamma pathway gene expression in tumor cells as mechanism of immune escape of colorectal carcinoma - Britzen-Laurent, Nathalie; Straube, Julia; Waldner, Maximilian; Becker, Christoph; Croner, Roland; Pilarsky, Christian; Merkel, Susanne; Stürzl, Michael (CANCER RESEARCH, 2018)
CRIS-Team WoS Importer:2019-06-18

MED12 loss activates endogenous retroelements to sensitise immunotherapy in pancreatic cancer - Tang, Yingying; Tang, Shijie; Yang, Wenjuan; Zhang, Zhengyan; Wang, Teng; Wu, Yuyun; Xu, Junyi; Pilarsky, Christian; Mazzone, Massimiliano; Wang, Lei Wei; Sun, Yongwei; Tian, Ruijun; et al. (Gut, 2024)
Objective Pancreatic ductal adenocarcinoma (PDAC) stands as one of the most lethal cancers, marked by its lethality and limited treatment options, including the utilisation of checkpoint blockade (ICB) immunotherapy. Epigenetic dysregulation is a defining feature of tumourigenesis that is implicated in immune surveillance, but remains elusive in PDAC. Design To identify the factors that modulate immune surveillance, we employed in vivo epigenetic-focused CRISPR-Cas9 screen in mouse PDAC tumour models engrafted in either immunocompetent or immunodeficient mice. Results Here, we identified MED12 as a top hit, emerging as a potent negative modulator of immune tumour microenviroment (TME) in PDAC. Loss of Med12 significantly promoted infiltration and cytotoxicity of immune cells including CD8+ T cells, natural killer (NK) and NK1.1+ T cells in tumours, thereby heightening the sensitivity of ICB treatment in a mouse model of PDAC. Mechanistically, MED12 stabilised heterochromatin protein HP1A to repress H3K9me3-marked endogenous retroelements. The derepression of retrotransposons induced by MED12 loss triggered cytosolic nucleic acid sensing and subsequent activation of type I interferon pathways, ultimately leading to robust inflamed TME . Moreover, we uncovered a negative correlation between MED12 expression and immune resposne pathways, retrotransposon levels as well as the prognosis of patients with PDAC undergoing ICB therapy. Conclusion In summary, our findings underscore the pivotal role of MED12 in remodelling immnue TME through the epigenetic silencing of retrotransposons, offering a potential therapeutic target for enhancing tumour immunogenicity and overcoming immunotherapy resistance in PDAC.
CRIS-Team Scopus Importer:2024-09-27

Meeting Medical Need - Development of a High-Throughput Assay Using Pancreatic Cancer Patient Derived Organoids as a Tool for Personalized Medicine - Sankarasubramanian, Sushmitha; Niethard, Maya; Pilarsky, Christian; Regenbrecht, Christian; Wedeken, Lena (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Metabolic biomarker signature to differentiate pancreatic ductal adenocarcinoma from chronic pancreatitis - Mayerle, Julia; Kalthoff, Holger; Reszka, Regina; Kamlage, Beate; Peter, Erik; Schniewind, Bodo; Maldonado, Sandra González; Pilarsky, Christian; Heidecke, Claus Dieter; Schatz, Philipp; Distler, Marius; Scheiber, Jonas A.; et al. (Gut, 2017)
Current non-invasive diagnostic tests can distinguish between pancreatic cancer (pancreatic ductal adenocarcinoma (PDAC)) and chronic pancreatitis (CP) in only about two thirds of patients. We have searched for blood-derived metabolite biomarkers for this diagnostic purpose.For a case-control study in three tertiary referral centres, 914 subjects were prospectively recruited with PDAC (n=271), CP (n=282), liver cirrhosis (n=100) or healthy as well as non-pancreatic disease controls (n=261) in three consecutive studies. Metabolomic profiles of plasma and serum samples were generated from 477 metabolites identified by gas chromatography-mass spectrometry and liquid chromatography-tandem mass spectrometry.A biomarker signature (nine metabolites and additionally CA19-9) was identified for the differential diagnosis between PDAC and CP. The biomarker signature distinguished PDAC from CP in the training set with an area under the curve (AUC) of 0.96 (95% CI 0.93-0.98). The biomarker signature cut-off of 0.384 at 85% fixed specificity showed a sensitivity of 94.9% (95% CI 87.0%-97.0%). In the test set, an AUC of 0.94 (95% CI 0.91-0.97) and, using the same cut-off, a sensitivity of 89.9% (95% CI 81.0%-95.5%) and a specificity of 91.3% (95% CI 82.8%-96.4%) were achieved, successfully validating the biomarker signature.In patients with CP with an increased risk for pancreatic cancer (cumulative incidence 1.95%), the performance of this biomarker signature results in a negative predictive value of 99.9% (95% CI 99.7%-99.9%) (training set) and 99.8% (95% CI 99.6%-99.9%) (test set). In one third of our patients, the clinical use of this biomarker signature would have improved diagnosis and treatment stratification in comparison to CA19-9.
EVALuna2:15284

Metabolic impairment of non-small cell lung cancers by mitochondrial HSPD1 targeting - Parma, Beatrice; Ramesh, Vignesh; Gollavilli, Paradesi Naidu; Siddiqui, Aarif; Pinna, Luisa; Schwab, Annemarie; Marschall, Sabine; Zhang, Shuman; Pilarsky, Christian; Napoli, Francesca; Volante, Marco; Urbanczyk, Sophia; et al. (Journal of Experimental & Clinical Cancer Research, 2021)
Background The identification of novel targets is of paramount importance to develop more effective drugs and improve the treatment of non-small cell lung cancer (NSCLC), the leading cause of cancer-related deaths worldwide. Since cells alter their metabolic rewiring during tumorigenesis and along cancer progression, targeting key metabolic players and metabolism-associated proteins represents a valuable approach with a high therapeutic potential. Metabolic fitness relies on the functionality of heat shock proteins (HSPs), molecular chaperones that facilitate the correct folding of metabolism enzymes and their assembly in macromolecular structures. Methods Gene fitness was determined by bioinformatics analysis from available datasets from genetic screenings. HSPD1 expression was evaluated by immunohistochemistry from formalin-fixed paraffin-embedded tissues from NSCLC patients. Real-time proliferation assays with and without cytotoxicity reagents, colony formation assays and cell cycle analyses were used to monitor growth and drug sensitivity of different NSCLC cells in vitro. In vivo growth was monitored with subcutaneous injections in immune-deficient mice. Cell metabolic activity was analyzed through extracellular metabolic flux analysis. Specific knockouts were introduced by CRISPR/Cas9. Results We show heat shock protein family D member 1 (HSPD1 or HSP60) as a survival gene ubiquitously expressed in NSCLC and associated with poor patients' prognosis. HSPD1 knockdown or its chemical disruption by the small molecule KHS101 induces a drastic breakdown of oxidative phosphorylation, and suppresses cell proliferation both in vitro and in vivo. By combining drug profiling with transcriptomics and through a whole-genome CRISPR/Cas9 screen, we demonstrate that HSPD1-targeted anti-cancer effects are dependent on oxidative phosphorylation and validated molecular determinants of KHS101 sensitivity, in particular, the creatine-transporter SLC6A8 and the subunit of the cytochrome c oxidase complex COX5B. Conclusions These results highlight mitochondrial metabolism as an attractive target and HSPD1 as a potential theranostic marker for developing therapies to combat NSCLC.
CRIS-Team WoS Importer:2021-08-20

Microbiome Patterns in Matched Bile, Duodenal, Pancreatic Tumor Tissue, Drainage, and Stool Samples: Association with Preoperative Stenting and Postoperative Pancreatic Fistula Development - Langheinrich, Melanie; Wirtz, Stefan; Kneis, Barbara; Gittler, Matthias M.; Tyc, Olaf; Schierwagen, Robert; Brunner, Maximilian; Krautz, Christian; Pilarsky, Christian; Trebicka, Jonel; Agaimy, Abbas; Grützmann, Robert; et al. (Journal of Clinical Medicine, 2020)
Postoperative complications after pancreatic surgery are still a significant problem in clinical practice. The aim of this study was to characterize and compare the microbiomes of different body compartments (bile duct, duodenal mucosa, pancreatic tumor lesion, postoperative drainage fluid, and stool samples; preoperative and postoperative) in patients undergoing pancreatic surgery for suspected pancreatic cancer, and their association with relevant clinical factors (stent placement, pancreatic fistula, and gland texture). For this, solid (duodenal mucosa, pancreatic tumor tissue, stool) and liquid (bile, drainage fluid) biopsy samples of 10 patients were analyzed using 16s rRNA gene next-generation sequencing. Our analysis revealed: (i) a distinct microbiome in the different compartments, (ii) markedly higher abundance of Enterococcus in patients undergoing preoperative stent placement in the common bile duct, (iii) significant differences in the beta diversity between patients who developed a postoperative pancreatic fistula (POPF B/C), (iv) patients with POPF B/C were more likely to have bacteria belonging to the genus Enterococcus, and (v) differences in microbiome composition with regard to the pancreatic gland texture. The structure of the microbiome is distinctive in different compartments, and can be associated with the development of a postoperative pancreatic fistula.
CRIS-Team WoS Importer:2020-11-06

Microfluidics applications for high-throughput single cell sequencing - Zhou, Wen-Min; Yan, Yan-Yan; Guo, Qiao-Ru; Ji, Hong; Wang, Hui; Xu, Tian-Tian; Makabel, Bolat; Pilarsky, Christian; He, Gen; Yu, Xi-Yong; Zhang, Jian-Ye (Journal of Nanobiotechnology, 2021)
The inherent heterogeneity of individual cells in cell populations plays significant roles in disease development and progression, which is critical for disease diagnosis and treatment. Substantial evidences show that the majority of traditional gene profiling methods mask the difference of individual cells. Single cell sequencing can provide data to characterize the inherent heterogeneity of individual cells, and reveal complex and rare cell populations. Different microfluidic technologies have emerged for single cell researches and become the frontiers and hot topics over the past decade. In this review article, we introduce the processes of single cell sequencing, and review the principles of microfluidics for single cell analysis. Also, we discuss the common high-throughput single cell sequencing technologies along with their advantages and disadvantages. Lastly, microfluidics applications in single cell sequencing technology for the diagnosis of cancers and immune system diseases are briefly illustrated. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2021-10-29
Keywords: Biomedical applications; Droplets; High-throughput; Microfluidic; Single cell RNA sequencing (scRNA-seq); Single cell separation

Microfluidic Technology for the Isolation and Analysis of Exosomes - Wu, Yusong; Wang, Yuqing; Lu, Yanjun; Luo, Xiaomei; Huang, Yinghong; Xie, Ting; Pilarsky, Christian; Dang, Yuanye; Zhang, Jianye (Micromachines, 2022)
Exosomes are lipid-bilayer enclosed vesicles with diameters of 30–150 nm, which play a pivotal role in cell communication by transporting their cargoes such as proteins, lipids, and genetic materials. In recent years, exosomes have been under intense investigation, as they show great promise in numerous areas, especially as bio-markers in liquid biopsies. However, due to the high heterogeneity and the nano size of exosomes, the separation of exosomes is not easy. This review will deliver an outline of the conventional methods and the microfluidic-based technologies for exosome separation. Particular attention is devoted to microfluidic devices, highlighting the efficiency of exosome isolation by these methods. Additionally, this review will introduce advances made in the integrated microfluidics technologies that enable the separation and analysis of exosomes.
CRIS-Team Scopus Importer:2022-11-11
Keywords: detection; exosomes; extra-cellular vesicle; isolation; microfluidics

MiR-132 controls pancreatic beta cell proliferation and survival through Pten/Akt/Foxo3 signaling - Mziaut, Hassan; Henniger, Georg; Ganss, Katharina; Hempel, Sebastian; Wolk, Steffen; McChord, Johanna; Chowdhury, Kamal; Ravassard, Philippe; Knoch, Klaus Peter; Krautz, Christian; Weitz, Jürgen; Grützmann, Robert; et al. (Molecular Metabolism, 2020)
Objective: MicroRNAs (miRNAs) play an integral role in maintaining beta cell function and identity. Deciphering their targets and precise role, however, remains challenging. In this study, we aimed to identify miRNAs and their downstream targets involved in the regeneration of islet beta cells following partial pancreatectomy in mice. Methods: RNA from laser capture microdissected (LCM) islets of partially pancreatectomized and sham-operated mice were profiled with microarrays to identify putative miRNAs implicated in beta cell regeneration. Altered expression of the selected miRNAs, including miR-132, was verified by RT-PCR. Potential targets of miR-132 were selected through bioinformatic data mining. Predicted miR-132 targets were validated for their changed RNA, protein expression levels, and signaling upon miR-132 knockdown and/or overexpression in mouse MIN6 and human EndoC-βH1 insulinoma cells. The ability of miR-132 to foster beta cell proliferation in vivo was further assessed in pancreatectomized miR-132−/− and control mice. Results: Partial pancreatectomy significantly increased the number of BrdU+/insulin+ islet cells. Microarray profiling revealed that 14 miRNAs, including miR-132 and -141, were significantly upregulated in the LCM islets of the partially pancreatectomized mice compared to the LCM islets of the control mice. In the same comparison, miR-760 was the only downregulated miRNA. The changed expression of these miRNAs in the islets of the partially pancreatectomized mice was confirmed by RT-PCR only in the case of miR-132 and -141. Based on previous knowledge of its function, we focused our attention on miR-132. Downregulation of miR-132 reduced the proliferation of MIN6 cells while enhancing the levels of pro-apoptotic cleaved caspase-9. The opposite was observed in miR-132 overexpressing MIN6 cells. Microarray profiling, RT-PCR, and immunoblotting of the latter cells demonstrated their downregulated expression of Pten with concomitant increased levels of pro-proliferative factors phospho-Akt and phospho-Creb and inactivation of pro-apoptotic Foxo3a via its phosphorylation. Downregulation of Pten was further confirmed in the LCM islets of pancreatectomized mice compared to the sham-operated mice. Moreover, overexpression of miR-132 correlated with increased proliferation of EndoC-βH1 cells. The regeneration of beta cells following partial pancreatectomy was lower in the miR-132/212−/− mice than the control littermates. Conclusions: This study provides compelling evidence about the critical role of miR-132 for the regeneration of mouse islet beta cells through the downregulation of its target Pten. Hence, the miR-132/Pten/Akt/Foxo3 signaling pathway may represent a suitable target to enhance beta cell mass.
CRIS-Team Scopus Importer:2019-12-24
Keywords: Apoptosis; miR-132; Pancreatectomy; Pten/Akt/Foxo3a; β cell regeneration

Mitoxantrone and Mitoxantrone-Loaded Iron Oxide Nanoparticles Induce Cell Death in Human Pancreatic Ductal Adenocarcinoma Cell Spheroids - Dinter, Jonas; Friedrich, Ralf P.; Yang, Hai; Pilarsky, Christian; Mangge, Harald; Pöttler, Marina; Janko, Christina; Alexiou, Christoph; Lyer, Stefan (Materials, 2023)
Pancreatic ductal adenocarcinoma is a hard-to-treat, deadly malignancy. Traditional treatments, such as surgery, radiation and chemotherapy, unfortunately are still not able to significantly improve long-term survival. Three-dimensional (3D) cell cultures might be a platform to study new drug types in a highly reproducible, resource-saving model within a relevant pathophysiological cellular microenvironment. We used a 3D culture of human pancreatic ductal adenocarcinoma cell lines to investigate a potential new treatment approach using superparamagnetic iron oxide nanoparticles (SPIONs) as a drug delivery system for mitoxantrone (MTO), a chemotherapeutic agent. We established a PaCa DD183 cell line and generated PANC-1SMAD4 (−/−) cells by using the CRISPR-Cas9 system, differing in a prognostically relevant mutation in the TGF-β pathway. Afterwards, we formed spheroids using PaCa DD183, PANC-1 and PANC-1SMAD4 (−/−) cells, and analyzed the uptake and cytotoxic effect of free MTO and MTO-loaded SPIONs by microscopy and flow cytometry. MTO and SPION–MTO-induced cell death in all tumor spheroids in a dose-dependent manner. Interestingly, spheroids with a SMAD4 mutation showed an increased uptake of MTO and SPION–MTO, while at the same time being more resistant to the cytotoxic effects of the chemotherapeutic agents. MTO-loaded SPIONs, with their ability for magnetic drug targeting, could be a future approach for treating pancreatic ductal adenocarcinomas.
CRIS-Team Scopus Importer:2023-04-28
Keywords: 3D cell culture; magnetic drug targeting; nanomedicine; pancreatic ductal adenocarcinoma; superparamagnetic iron oxide nanoparticles

Muscle‐derived cytokines reduce growth, viability and migratory activity of pancreatic cancer cells - Schwappacher, Raphaela; Dieterich, Walburga; Reljic, Dejan; Pilarsky, Christian; Mukhopadhyay, Debabrata; Chang, David K.; Biankin, Andrew; Siebler, Jürgen; Herrmann, Hans J.; Neurath, Markus; Zopf, Yurdagül (Cancers, 2021)
The evidence that regular physical exercise reduces the risk of developing cancer is well described. However, the interaction between physical exercise and cancer is not fully clarified yet. Several myokines released by skeletal muscle appear to have a direct anti‐tumour function. There are few data on myokine secretion after exercise in patients with advanced tumours. Pancreatic cancer (PC) is a very aggressive and usually fatal cancer. To investigate the effects of exercise in PC, the blood of advanced‐stage PC patients was analysed after 12 weeks of resistance training using whole‐body electromyostimulation. After the 12‐week training period, the patient serum inhibited the proliferation and the motility of PC cells and enhanced PC cell apoptosis. The impact of exercise training was also investigated in an exercise‐mimicking in vitro model using electric pulse stimulation of human myotubes and revealed similar anti‐tumour effects on PC cells, clearly indicating direct cancer‐protective properties of activated skeletal muscle. Protein and gene expression analyses in plasma from exercise‐trained patients and in myotube cultures after in vitro exercise showed that interleukin 10 (IL10), C‐X‐C motif ligand 1 (CXCL1) and C‐C motif chemokine ligand 4 (CCL4) are myokines released from activated skeletal muscle. In accordance with the effects of serum from exercise‐trained patients, the supplementation with recombinant IL10, CXCL1 and CCL4 impaired growth and migration of PC cells. Treatment of PC cells with these myokines upregulated caspase 3/7 expression and the cleavage of poly(ADP‐ribose) polymerase, leading to enhanced PC cell death. The identification of myokines with anti‐tumour properties in advanced‐stage PC patients after exercise opens a new perspective in supportive therapy with sports and exercise for cancer patients.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Apoptosis; Electric pulse stimulation; Exercise; Migration; Myokine; Pancreatic cancer; Physical activity; Proliferation; Whole‐body electromyostimulation

MYC ecDNA promotes intratumour heterogeneity and plasticity in PDAC - Fiorini, Elena; Malinova, Antonia; Schreyer, Daniel; Pasini, Davide; Bevere, Michele; Alessio, Giorgia; Rosa, Diego; D’Agosto, Sabrina; Azzolin, Luca; Milite, Salvatore; Andreani, Silvia; Lupo, Francesca; et al. (Nature, 2025)
Intratumour heterogeneity and phenotypic plasticity drive tumour progression and therapy resistance1,2. Oncogene dosage variation contributes to cell-state transitions and phenotypic heterogeneity3, thereby providing a substrate for somatic evolution. Nonetheless, the genetic mechanisms underlying phenotypic heterogeneity are still poorly understood. Here we show that extrachromosomal DNA (ecDNA) is a major source of high-level focal amplification in key oncogenes and a major contributor of MYC heterogeneity in pancreatic ductal adenocarcinoma (PDAC). We demonstrate that ecDNAs drive varying levels of MYC dosage, depending on their regulatory landscape, enabling cancer cells to rapidly and reversibly adapt to microenvironmental changes. In the absence of selective pressure, a high ecDNA copy number imposes a substantial fitness cost on PDAC cells. We also show that MYC dosage affects cell morphology and dependence of cancer cells on stromal niche factors. Our work provides a detailed analysis of ecDNAs in PDAC and describes a new genetic mechanism driving MYC heterogeneity in PDAC.
CRIS-Team Scopus Importer:2025-04-01

Netrank: network-based approach for biomarker discovery - Al-Fatlawi, Ali; Rusadze, Eka; Shmelkin, Alexander; Malekian, Negin; Ozen, Cigdem; Pilarsky, Christian; Schroeder, Michael (BMC Bioinformatics, 2023)
Background: Integrating multi-omics data is fast becoming a powerful approach for predicting disease progression and treatment outcomes. In light of that, we introduce a modified version of the NetRank algorithm, a network-based algorithm for biomarker discovery that incorporates the protein associations, co-expressions, and functions with its phenotypic association to differentiate different types of cancer. NetRank is introduced here as a robust feature selection method for biomarker selection in cancer prediction. We assess the robustness and suitability of the RNA gene expression data through scanning genomic data for 19 cancer types with more than 3000 patients from The Cancer Genome Atlas (TCGA). Results: The results of evaluating different cancer type profiles from the TCGA data demonstrate the strength of our approach to identifying interpretable biomarker signatures for cancer outcome prediction. NetRank’s biomarkers segregate most cancer types with an area under the curve (AUC) above 90% using compact signatures. Conclusion: In this paper we provide a fast and efficient implementation of NetRank, with a case study from The Cancer Genome Atlas, to assess the performance. We incorporated complete functionality for pre and post-processing for RNA-seq gene expression data with functions for building protein-protein interaction networks. The source code of NetRank is freely available (at github.com/Alfatlawi/Omics-NetRank) with an installable R library. We also deliver a comprehensive practical user manual with examples and data attached to this paper.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Biomarker; Cancer; Gene expression; Protein networks; R package; RNA

N-glycosylation Regulates Intrinsic IFN-γ Resistance in Colorectal Cancer: Implications for Immunotherapy - Krug, Julia; Rodrian, Gabriele; Petter, Katja; Yang, Hai; Khoziainova, Svetlana; Guo, Wei; Benard, Alan; Merkel, Susanne; Gellert, Susan; Maschauer, Simone; Spermann, Monika; Waldner, Maximilian; et al. (Gastroenterology, 2023)
Background & AIMS: Advanced colorectal carcinoma (CRC) is characterized by a high frequency of primary immune evasion and refractoriness to immunotherapy. Given the importance of interferon (IFN)-γ in CRC immunosurveillance, we investigated whether and how acquired IFN-γ resistance in tumor cells would promote tumor growth, and whether IFN-γ sensitivity could be restored. Methods: Spontaneous and colitis-associated CRC development was induced in mice with a specific IFN-γ pathway inhibition in intestinal epithelial cells. The influence of IFN-γ pathway gene status and expression on survival was assessed in patients with CRC. The mechanisms underlying IFN-γ resistance were investigated in CRC cell lines. Results: The conditional knockout of the IFN-γ receptor in intestinal epithelial cells enhanced spontaneous and colitis-associated colon tumorigenesis in mice, and the loss of IFN-γ receptor α (IFNγRα) expression by tumor cells predicted poor prognosis in patients with CRC. IFNγRα expression was repressed in human CRC cells through changes in N-glycosylation, which decreased protein stability via proteasome-dependent degradation, inhibiting IFNγR-signaling. Downregulation of the bisecting N-acetylglucosaminyltransferase III (MGAT3) expression was associated with IFN-γ resistance in all IFN-γ–resistant cells, and highly correlated with low IFNγRα expression in CRC tissues. Both ectopic and pharmacological reconstitution of MGAT3 expression with all-trans retinoic acid increased bisecting N-glycosylation, as well as IFNγRα protein stability and signaling. Conclusions: Together, our results demonstrated that tumor-associated changes in N-glycosylation destabilize IFNγRα, causing IFN-γ resistance in CRC. IFN-γ sensitivity could be reestablished through the increase in MGAT3 expression, notably via all-trans retinoic acid treatment, providing new prospects for the treatment of immune-resistant CRC.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Colon Cancer; IFNGR1; Immune Evasion

Plasma extracellular vesicle messenger RNA profiling identifies prognostic EV signature for non-invasive risk stratification for survival prediction of patients with pancreatic ductal adenocarcinoma - Han, Yi; Drobisch, Pascal; Krüger, Alexander; William, Doreen; Grützmann, Konrad; Böthig, Lukas; Polster, Heike; Seifert, Lena; Seifert, Adrian M.; Distler, Marius; Pecqueux, Mathieu; Riediger, Carina; et al. (Journal of Hematology & Oncology, 2023)
Background: The prognosis of pancreatic ductal adenocarcinoma (PDAC) is one of the most dismal of all cancers and the median survival of PDAC patients is only 6–8 months after diagnosis. While decades of research effort have been focused on early diagnosis and understanding of molecular mechanisms, few clinically useful markers have been universally applied. To improve the treatment and management of PDAC, it is equally relevant to identify prognostic factors for optimal therapeutic decision-making and patient survival. Compelling evidence have suggested the potential use of extracellular vesicles (EVs) as non-invasive biomarkers for PDAC. The aim of this study was thus to identify non-invasive plasma-based EV biomarkers for the prediction of PDAC patient survival after surgery. Methods: Plasma EVs were isolated from a total of 258 PDAC patients divided into three independent cohorts (discovery, training and validation). RNA sequencing was first employed to identify differentially-expressed EV mRNA candidates from the discovery cohort (n = 65) by DESeq2 tool. The candidates were tested in a training cohort (n = 91) by digital droplet polymerase chain reaction (ddPCR). Cox regression models and Kaplan–Meier analyses were used to build an EV signature which was subsequently validated on a multicenter cohort (n = 83) by ddPCR. Results: Transcriptomic profiling of plasma EVs revealed differentially-expressed mRNAs between long-term and short-term PDAC survivors, which led to 10 of the top-ranked candidate EV mRNAs being tested on an independent training cohort with ddPCR. The results of ddPCR enabled an establishment of a novel prognostic EV mRNA signature consisting of PPP1R12A, SCN7A and SGCD for risk stratification of PDAC patients. Based on the EV mRNA signature, PDAC patients with high risk displayed reduced overall survival (OS) rates compared to those with low risk in the training cohort (p = 0.014), which was successfully validated on another independent cohort (p = 0.024). Interestingly, the combination of our signature and tumour stage yielded a superior prognostic performance (p = 0.008) over the signature (p = 0.022) or tumour stage (p = 0.016) alone. It is noteworthy that the EV mRNA signature was demonstrated to be an independent unfavourable predictor for PDAC prognosis. Conclusion: This study provides a novel and non-invasive prognostic EV mRNA signature for risk stratification and survival prediction of PDAC patients.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Extracellular vesicles; mRNA biomarkers; Pancreatic ductal adenocarcinoma; Plasma extracellular vesicle; Prognosis

Plasma Metabolic Profiling Identify Metabolic Subtypes of Pancreatic Ductal Adenocarcinoma - Mahajan, U. M.; Alnatsha, A.; Li, Q.; Oehrle, B.; Weiss, U.; Sendler, M.; Distler, M.; Uhl, W.; Fahlbusch, T.; Goni, E.; Beyer, G.; Chromik, A.; et al. (PANCREAS, 2021)
CRIS-Team WoS Importer:2021-10-29

Plasma Metabolome Profiling Identifies Metabolic Subtypes of Pancreatic Ductal Adenocarcinoma - Mahajan, Ujjwal Mukund; Alnatsha, Ahmed; Li, Qi; Oehrle, Bettina; Weiss, Frank-Ulrich; Sendler, Matthias; Distler, Marius; Uhl, Waldemar; Fahlbusch, Tim; Goni, Elisabetta; Beyer, Georg; Chromik, Ansgar; et al. (Cells, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest cancers. Developing biomarkers for early detection and chemotherapeutic response prediction is crucial to improve the dismal prognosis of PDAC patients. However, molecular cancer signatures based on transcriptome analysis do not reflect intratumoral heterogeneity. To explore a more accurate stratification of PDAC phenotypes in an easily accessible matrix, plasma metabolome analysis using MxP(R) Global Profiling and MxP(R) Lipidomics was performed in 361 PDAC patients. We identified three metabolic PDAC subtypes associated with distinct complex lipid patterns. Subtype 1 was associated with reduced ceramide levels and a strong enrichment of triacylglycerols. Subtype 2 demonstrated increased abundance of ceramides, sphingomyelin and other complex sphingolipids, whereas subtype 3 showed decreased levels of sphingolipid metabolites in plasma. Pathway enrichment analysis revealed that sphingolipid-related pathways differ most among subtypes. Weighted correlation network analysis (WGCNA) implied PDAC subtypes differed in their metabolic programs. Interestingly, a reduced expression among related pathway genes in tumor tissue was associated with the lowest survival rate. However, our metabolic PDAC subtypes did not show any correlation to the described molecular PDAC subtypes. Our findings pave the way for further studies investigating sphingolipids metabolisms in PDAC.
CRIS-Team WoS Importer:2021-08-06

Precision Oncology in Surgery: Patient Selection for Operable Pancreatic Cancer - Dreyer, Stephan B; Pinese, Mark; Jamieson, Nigel B.; Scarlett, Christopher J; Colvin, Emily K; Pajic, Marina; Johns, Amber L.; Humphris, Jeremy; Wu, Jianmin; Cowley, Mark J.; Chou, Angela; Nagrial, Adnan M.; et al. (Annals of Surgery, 2018)
OBJECTIVE: We aimed to define preoperative clinical and molecular characteristics that would allow better patient selection for operative resection. BACKGROUND: Although we use molecular selection methods for systemic targeted therapies, these principles are not applied to surgical oncology. Improving patient selection is of vital importance for the operative treatment of pancreatic cancer (pancreatic ductal adenocarcinoma). Although surgery is the only chance of long-term survival, 80% still succumb to the disease and approximately 30% die within 1 year, often sooner than those that have unresected local disease. METHOD: In 3 independent pancreatic ductal adenocarcinoma cohorts (total participants = 1184) the relationship between aberrant expression of prometastatic proteins S100A2 and S100A4 and survival was assessed. A preoperative nomogram based on clinical variables available before surgery and expression of these proteins was constructed and compared to traditional measures, and a postoperative nomogram. RESULTS: High expression of either S100A2 or S100A4 was independent poor prognostic factors in a training cohort of 518 participants. These results were validated in 2 independent patient cohorts (Glasgow, n = 198; Germany, n = 468). Aberrant biomarker expression stratified the cohorts into 3 distinct prognostic groups. A preoperative nomogram incorporating S100A2 and S100A4 expression predicted survival and nomograms derived using postoperative clinicopathological variables. CONCLUSIONS: Of those patients with a poor preoperative nomogram score, approximately 50% of patients died within a year of resection. Nomograms have the potential to improve selection for surgery and neoadjuvant therapy, avoiding surgery in aggressive disease, and justifying more extensive resections in biologically favorable disease.
EVALuna2:212801

Pre-clinical Models of Metastasis in Pancreatic Cancer - Miquel Sedo, Maria; Zhang, Shuman; Pilarsky, Christian (Frontiers in Cell and Developmental Biology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is a hostile solid malignancy coupled with an extremely high mortality rate. Metastatic disease is already found in most patients at the time of diagnosis, resulting in a 5-year survival rate below 5%. Improved comprehension of the mechanisms leading to metastasis is pivotal for the development of new targeted therapies. A key field to be improved are modeling strategies applied in assessing cancer progression, since traditional platforms fail in recapitulating the complexity of PDAC. Consequently, there is a compelling demand for new preclinical models that mirror tumor progression incorporating the pressure of the immune system, tumor microenvironment, as well as molecular aspects of PDAC. We suggest the incorporation of 3D organoids derived from genetically engineered mouse models or patients as promising new tools capable to transform PDAC pre-clinical modeling and access new frontiers in personalized medicine.
CRIS-Team Scopus Importer:2021-11-19
Keywords: GEMMs; metastasis; metastasis models; organoids; pancreatic cancer; PDAC – pancreatic ductal adenocarcinoma

Roflumilast inhibits tumor growth and migration in STK11/LKB1 deficient pancreatic cancer - Zhang, Shuman; Yun, Duo; Yang, Hao; Eckstein, Markus; Elbait, Gihan Daw; Zhou, Yaxing; Lu, Yanxi; Yang, Hai; Zhang, Jinping; Dörflein, Isabella; Britzen-Laurent, Nathalie; Pfeffer, Susanne; et al. (Cell Death Discovery, 2024)
Pancreatic cancer is a malignant tumor of the digestive system. It is highly aggressive, easily metastasizes, and extremely difficult to treat. This study aimed to analyze the genes that might regulate pancreatic cancer migration to provide an essential basis for the prognostic assessment of pancreatic cancer and individualized treatment. A CRISPR knockout library directed against 915 murine genes was transfected into TB 32047 cell line to screen which gene loss promoted cell migration. Next-generation sequencing and PinAPL.py- analysis was performed to identify candidate genes. We then assessed the effect of serine/threonine kinase 11 (STK11) knockout on pancreatic cancer by wound-healing assay, chick agnosia (CAM) assay, and orthotopic mouse pancreatic cancer model. We performed RNA sequence and Western blotting for mechanistic studies to identify and verify the pathways. After accelerated Transwell migration screening, STK11 was identified as one of the top candidate genes. Further experiments showed that targeted knockout of STK11 promoted the cell migration and increased liver metastasis in mice. Mechanistic analyses revealed that STK11 knockout influences blood vessel morphogenesis and is closely associated with the enhanced expression of phosphodiesterases (PDEs), especially PDE4D, PDE4B, and PDE10A. PDE4 inhibitor Roflumilast inhibited STK11-KO cell migration and tumor size, further demonstrating that PDEs are essential for STK11-deficient cell migration. Our findings support the adoption of therapeutic strategies, including Roflumilast, for patients with STK11-mutated pancreatic cancer in order to improve treatment efficacy and ultimately prolong survival.
CRIS-Team Scopus Importer:2024-04-12

Scribble Deficiency Promotes Pancreatic Ductal Adenocarcinoma Development and Metastasis - Bermejo-Rodriguez, Camino; Araos Henríquez, Joaquín; Caligiuri, Giuseppina; Pinto Teles, Sara; Park, Youngkyu; Evans, Anthony; Barrera, Lawrence N.; Neesse, Albrecht; Grützmann, Robert; Aust, Daniela; Rümmele, Petra; Knösel, Thomas; et al. (Cancer Research, 2024)
Perturbation of cell polarity is a hallmark of pancreatic ductal adenocarcinoma (PDAC) progression. Scribble (SCRIB) is a well-characterized polarity regulator that has diverse roles in the pathogenesis of human neoplasms. To investigate the impact of SCRIB deficiency in PDAC development and progression, Scrib expression was genetically ablated in well-established mouse models of PDAC. Scrib loss in combination with KrasG12D did not influence development of pancreatic intraepithelial neoplasms in mice. However, Scrib deletion cooperated with KrasG12D and concomitant Trp53 heterozygous deletion to promote invasive PDAC and metastatic dissemination, leading to reduced overall survival. Immunohistochemical and transcriptome analyses revealed that Scrib-null tumors display a pronounced reduction of collagen content and an abundance of cancer-associated fibroblasts (CAF). Mechanistically, IL1α levels were reduced in Scrib-deficient tumors, and Scrib knockdown downregulated IL1α in mouse PDAC organoids (mPDO), which impaired CAF activation. Furthermore, Scrib loss increased YAP activation in mPDOs and established PDAC cell lines, enhancing cell survival. Clinically, SCRIB expression was decreased in human PDAC, and SCRIB mislocalization was associated with poorer patient outcome. These results indicate that SCRIB deficiency enhances cancer cell survival and remodels the tumor microenvironment to accelerate PDAC development and progression, establishing the tumor suppressor function of SCRIB in advanced pancreatic cancer. Significance: SCRIB loss promotes invasive pancreatic cancer development via both cell-autonomous and non-cell-autonomous processes and is associated with poorer outcomes, denoting SCRIB as a tumor suppressor and potential biomarker for the prediction of recurrence.
CRIS-Team Scopus Importer:2024-09-27

Sequential ATR and PARP inhibition overcomes acquired DNA damaging agent resistance in pancreatic ductal adenocarcinoma - Herbert, Katharine J.; Upstill-Goddard, Rosie; Dreyer, Stephan B.; Rebus, Selma; Pilarsky, Christian; Debabrata, Mukhopadhyay; Lord, Christopher J.; Biankin, Andrew V.; Froeling, Fieke E.M.; Chang, David K. (British Journal of Cancer, 2025)
Background: Pancreatic ductal adenocarcinoma (PDAC) remains the most lethal cancer. While DNA damaging agents such as platinum and PARP inhibitors have derived clinical benefits, acquired resistance invariably develops. Hence there is an urgent need for novel therapeutic strategies to overcome acquired resistance. Methods: Clinically relevant resistance in PDAC patient-derived cell lines was achieved by extended exposure to chemotherapy agents. Synergy scoring, clonogenicity, flow cytometry, immunofluorescence, and transcriptomic analysis were used to investigate the efficacy of ATR (ceralasertib) and PARP (olaparib) inhibitors in overcoming acquired resistance. Results: Acquired resistance was associated with transcriptomic shifts in cell cycle checkpoint regulation, metabolic control, DNA damage response (DDR), programmed cell death, and the replication stress response. Combination treatment with ceralasertib, and olaparib was synergistic in all models of acquired resistance. Sequential use of ceralasertib prior to olaparib was highly effective at low dose for DDR proficient models, whereas DDR deficient models responded better with olaparib treatment first. Conclusions: We provide in vitro evidence of a novel therapeutic strategy to overcome acquired resistance to PARP inhibitor and platinum in PDAC, using sequential exposure to ceralasertib and olaparib. A sequential regimen should be investigated clinically to circumvent dose limiting toxicity seen in concurrent combinations.
CRIS-Team Scopus Importer:2025-06-06

Silenced ZNF154 is associated with longer survival in resectable pancreatic cancer - Wiesmüller, Felix; Kopke, Josephin; Aust, Daniela; Roy, Janine; Dahl, Andreas; Pilarsky, Christian; Grützmann, Robert (International Journal of Molecular Sciences, 2019)
Pancreatic cancer has become the third leading cause of cancer-related death in the Western world despite advances in therapy of other cancerous lesions. Late diagnosis due to a lack of symptoms during early disease allows metastatic spread of the tumor. Most patients are considered incurable because of metastasized disease. On a cellular level, pancreatic cancer proves to be rather resistant to chemotherapy. Hence, early detection and new therapeutic targets might improve outcomes. The detection of DNA promoter hypermethylation has been described as a method to identify putative genes of interest in cancer entities. These genes might serve as either biomarkers or might lead to a better understanding of the molecular mechanisms involved. We checked tumor specimens from 80 patients who had undergone pancreatic resection for promoter hypermethylation of the zinc finger protein ZNF154. Then, we further characterized the effects of ZNF154 on cell viability and gene expression by in vitro experiments. We found a significant association between ZNF154 hypermethylation and better survival in patients with resectable pancreatic cancer. Moreover, we suspect that the cell growth suppressor SLFN5 might be linked to a silenced ZNF154 in pancreatic cancer.
CRIS-Team Scopus Importer:2019-11-12
Keywords: Biomarker; DNA methylation; Methylation-specific PCR; Pancreatic cancer; PDAC; SLFN5; ZNF154

Simultaneous gene silencing of KRAS and anti-apoptotic genes as a multitarget therapy - Werner, Kristin; Lademann, Franziska; Thepkaysone, May-Linn; Jahnke, Beatrix; Aust, Daniela; Kahlert, Christoph; Weitz, Juergen; Grützmann, Robert; Pilarsky, Christian; Pilarsky, Christian; Weber, Georg (Oncotarget, 2016)
Pancreatic cancer is one of the most lethal tumor types worldwide and an effective therapy is still elusive. Targeted therapy focused against a specific alteration is by definition unable to attack broad pathway signaling modification. Tumor heterogeneity will render targeted therapies ineffective based on the regrowth of cancer cell sub-clones. Therefore multimodal therapy strategies, targeting signaling pathways simultaneously should improve treatment.SiRNAs against KRAS and the apoptosis associated genes BCLXL, FLIP, MCL1L, SURVIVIN and XIAP were transfected into human and murine pancreatic cancer cell lines. Induction of apoptosis was measured by Caspase 3/7 activation, subG1 FACS analysis and PARP cleavage. The therapeutic approach was tested in a subcutaneous allograft model with a murine cancer cell line.By using siRNAs as a systematic approach to remodel signal transduction in pancreatic cancer the results showed increasing inhibition of proliferation and apoptosis induction in vitro and in vivo. Thus, siRNAs are suitable to model multimodal therapy against signaling pathways in pancreatic cancer. Improvements in in vivo delivery of siRNAs against a multitude of targets might therefore be a potential therapeutic approach.
EVALuna2:15258

Targeting DNA Damage Response and Replication Stress in Pancreatic Cancer - Dreyer, Stephan B.; Upstill-Goddard, Rosie; Paulus-Hock, Viola; Paris, Clara; Lampraki, Eirini Maria; Dray, Eloise; Serrels, Bryan; Caligiuri, Giuseppina; Rebus, Selma; Plenker, Dennis; Galluzzo, Zachary; Brunton, Holly; et al. (Gastroenterology, 2021)
Background & Aims: Continuing recalcitrance to therapy cements pancreatic cancer (PC) as the most lethal malignancy, which is set to become the second leading cause of cancer death in our society. The study aim was to investigate the association between DNA damage response (DDR), replication stress, and novel therapeutic response in PC to develop a biomarker-driven therapeutic strategy targeting DDR and replication stress in PC. Methods: We interrogated the transcriptome, genome, proteome, and functional characteristics of 61 novel PC patient–derived cell lines to define novel therapeutic strategies targeting DDR and replication stress. Validation was done in patient-derived xenografts and human PC organoids. Results: Patient-derived cell lines faithfully recapitulate the epithelial component of pancreatic tumors, including previously described molecular subtypes. Biomarkers of DDR deficiency, including a novel signature of homologous recombination deficiency, cosegregates with response to platinum (P <.001) and PARP inhibitor therapy (P <.001) in vitro and in vivo. We generated a novel signature of replication stress that predicts response to ATR (P <.018) and WEE1 inhibitor (P <.029) treatment in both cell lines and human PC organoids. Replication stress was enriched in the squamous subtype of PC (P <.001) but was not associated with DDR deficiency. Conclusions: Replication stress and DDR deficiency are independent of each other, creating opportunities for therapy in DDR-proficient PC and after platinum therapy.
CRIS-Team Scopus Importer:2020-12-25
Keywords: DNA Damage Response; Pancreatic Cancer; Personalized Medicine; Replication Stress

The cross-talk between the macro and micro-environment in precursor lesions of pancreatic cancer leads to new and promising circulating biomarkers - Mottini, Carla; Auciello, Francesca Romana; Manni, Isabella; Pilarsky, Christian; Caputo, Damiano; Caracciolo, Giulio; Rossetta, Alessandro; Di Gennaro, Elena; Budillon, Alfredo; Blandino, Giovanni; Roca, Maria Serena; Piaggio, Giulia (Journal of Experimental & Clinical Cancer Research, 2024)
Pancreatic cancer (PC) is a clinically challenging tumor to combat due to its advanced stage at diagnosis as well as its resistance to currently available therapies. The absence of early symptoms and known detectable biomarkers renders this disease incredibly difficult to detect/manage. Recent advances in the understanding of PC biology have highlighted the importance of cancer-immune cell interactions, not only in the tumor micro-environment but also in distant systemic sites, like the bone marrow, spleen and circulating immune cells, the so-called macro-environment. The response of the macro-environment is emerging as a determining factor in tumor development by contributing to the formation of an increasingly immunogenic micro-environment promoting tumor homeostasis and progression. We will summarize the key events associated with the feedback loop between the tumor immune micro-environment (TIME) and the tumor immune macroenvironment (TIMaE) in pancreatic precancerous lesions along with how it regulates disease development and progression. In addition, liquid biopsy biomarkers capable of diagnosing PC at an early stage of onset will also be discussed. A clearer understanding of the early crosstalk between micro-environment and macro-environment could contribute to identifying new molecular therapeutic targets and biomarkers, consequently improving early PC diagnosis and treatment.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Circulating biomarkers; Immune landscape; Macro-environment; Micro-environment; Pancreatic cancer

The Effect of GPRC5a on the Proliferation, Migration Ability, Chemotherapy Resistance, and Phosphorylation of GSK-3β in Pancreatic Cancer - Liu, Bin; Yang, Hai; Pilarsky, Christian; Weber, Georg (International Journal of Molecular Sciences, 2018)
Pancreatic cancer (PaCa) is the fourth leading cause of cancer-related death, and personalized targeted cancer therapy is becoming a promising treatment strategy for PaCa. The central approach of targeted therapy is to find a targetable key and an effective targeting method. In this study, the importance of GPRC5a (the G-protein-coupled receptor family C, member 5, group A) was identified using data mining methods based on published datasets. After analysis of the basic expression of GPRC5a in normal pancreas tissue and various PaCa cell lines, gene editing of GPRC5a in the human PaCa cell line MIA PaCa-2 and the mouse PaCa cell line TB32047 was performed using CRISPR/Cas9 (Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-associated proteins 9) to investigate the influence of GPRC5a on the proliferation and migration of PaCa cells as well as its effects on chemotherapy drug resistance. The results showed that GPRC5a was upregulated in PaCa tissues and various PaCa cell lines. Knockout of GPRC5a reduced the proliferation and migration ability of PaCa cell lines and suppressed the chemotherapy drug resistance of gemcitabine, oxaliplatin, and fluorouracil in PaCa cells. The phosphorylation of GSK-3β (Glycogen synthase kinase-3β) was found to be upregulated in the MIA PaCa-2 and TB32047 cells after GPRC5a knockout. In conclusion, GPRC5a was upregulated in PaCa leading to an enhanced drug resistance in PaCa cells. These results provide for the first time a theoretical basis for the development of an improved PaCa targeted therapy.
EVALuna2:210711

The EMT-activator Zeb1 is a key factor for cell plasticity and promotes metastasis in pancreatic cancer - Krebs, Angela M.; Mitschke, Julia; Losada, Maria Lasierra; Schmalhofer, Otto; Boerries, Melanie; Busch, Hauke; Böttcher, Martin; Mougiakakos, Dimitrios; Reichardt, Wilfried; Bronsert, Peter; Brunton, Valerie G.; Pilarsky, Christian; et al. (Nature Cell Biology, 2017)
Metastasis is the major cause of cancer-associated death. Partial activation of the epithelial-to-mesenchymal transition program (partial EMT) was considered a major driver of tumour progression from initiation to metastasis. However, the role of EMT in promoting metastasis has recently been challenged, in particular concerning effects of the Snail and Twist EMT transcription factors (EMT-TFs) in pancreatic cancer. In contrast, we show here that in the same pancreatic cancer model, driven by Pdx1-cre-mediated activation of mutant Kras and p53 (KPC model), the EMT-TF Zeb1 is a key factor for the formation of precursor lesions, invasion and notably metastasis. Depletion of Zeb1 suppresses stemness, colonization capacity and in particular phenotypic/metabolic plasticity of tumour cells, probably causing the observed in vivo effects. Accordingly, we conclude that different EMT-TFs have complementary subfunctions in driving pancreatic tumour metastasis. Therapeutic strategies should consider these potential specificities of EMT-TFs to target these factors simultaneously.

The glycan CA19-9 promotes pancreatitis and pancreatic cancer in mice - Engle, Dannielle D.; Tiriac, Herve; Rivera, Keith D.; Pommier, Arnaud; Whalen, Sean; Oni, Tobiloba E.; Alagesan, Brinda; Lee, Eun Jung; Yao, Melissa A.; Lucito, Matthew S.; Spielman, Benjamin; Da Silva, Brandon; et al. (Science, 2019)
Glycosylation alterations are indicative of tissue inflammation and neoplasia, but whether these alterations contribute to disease pathogenesis is largely unknown. To study the role of glycan changes in pancreatic disease, we inducibly expressed human fucosyltransferase 3 and b1,3-galactosyltransferase 5 in mice, reconstituting the glycan sialyl-Lewisa, also known as carbohydrate antigen 19-9 (CA19-9). Notably, CA19-9 expression in mice resulted in rapid and severe pancreatitis with hyperactivation of epidermal growth factor receptor (EGFR) signaling. Mechanistically, CA19-9 modification of the matricellular protein fibulin-3 increased its interaction with EGFR, and blockade of fibulin-3, EGFR ligands, or CA19-9 prevented EGFR hyperactivation in organoids. CA19-9–mediated pancreatitis was reversible and could be suppressed with CA19-9 antibodies. CA19-9 also cooperated with the KrasG12D oncogene to produce aggressive pancreatic cancer. These findings implicate CA19-9 in the etiology of pancreatitis and pancreatic cancer and nominate CA19-9 as a therapeutic target.
CRIS-Team Scopus Importer:2019-07-09

The glycan CA19-9 promotes pancreatitis and pancreatic cancer in mice - Engle, Dannielle; Tiriac, Herve; Rivera, Keith; Pommier, Arnaud; Whalen, Sean; Oni, Tobiloba; Alagesan, Brinda; Lee, Eun; Yao, Melissa; Lucito, Matthew; Spielman, Benjamin; Yu, Kenneth; et al. (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2020-05-02

The G Protein-Coupled Receptor RAI3 Is an Independent Prognostic Factor for Pancreatic Cancer Survival and Regulates Proliferation via STAT3 Phosphorylation - Jahny, Elisabeth; Yang, Hai; Liu, Bin; Jahnke, Beatrix; Lademann, Franziska; Knoesel, Thomas; Ruemmele, Petra; Grützmann, Robert; Aust, Daniela; Pilarsky, Christian; Denz, Axel (PLoS ONE, 2017)
Pancreatic Ductal Adenocarcinoma (PDAC) is one of the deadliest tumors worldwide. Understanding the function of gene expression alterations is a prerequisite for developing new strategies in diagnostic and therapy. GPRC5A (RAI3), coding for a seven transmembrane G protein-coupled receptor is known to be overexpressed in pancreatic cancer and might be an interesting candidate for therapeutic intervention. Expression levels of RAI3 were compared using a tissue microarray of 435 resected patients with pancreatic cancer as well as 209 samples from chronic pancreatitis (CP), intra-ductal papillary mucinous neoplasm (IPMN) and normal pancreatic tissue. To elucidate the function of RAI3 overexpression, siRNA based knock-down was used and transfected cells were analyzed using proliferation and migration assays. Pancreatic cancer patients showed a statistically significant overexpression of RAI3 in comparison to normal and chronic pancreatitis tissue. Especially the loss of apical RAI3 expression represents an independent prognostic parameter for overall survival of patients with pancreatic cancer. Suppression of GPRC5a results in decreased cell growth, proliferation and migration in pancreatic cancer cell lines via a STAT3 modulated pathway, independent from ERK activation.
EVALuna2:6846

The Role of Exosomes in Pancreatic Cancer - Lan, Bin; Zeng, Siyuan; Grützmann, Robert; Pilarsky, Christian (International Journal of Molecular Sciences, 2019)
Pancreatic cancer remains one of the deadliest cancers in the world, as a consequence of late diagnosis, early metastasis and limited response to chemotherapy, under which conditions the potential mechanism of pancreatic cancer progression requires further study. Exosomes are membrane vesicles which are important in the progression, metastasis and chemoresistance in pancreatic cancer. Additionally, they have been verified to be potential as biomarkers, targets and drug carriers for pancreatic cancer treatment. Thus, studying the role of exosomes in pancreatic cancer is significant. This paper focuses on the role of exosomes in the proliferation, metastasis and chemoresistance, as well as their potential applications for pancreatic cancer.
CRIS-Team Scopus Importer:2019-09-17
Keywords: biomarker; chemoresistance; exosomes; pancreatic cancer

The role of miR-200b/c in balancing EMT and proliferation revealed by an activity reporter - Gollavilli, Paradesi Naidu; Parma, Beatrice; Siddiqui, Aarif; Yang, Hai; Ramesh, Vignesh; Napoli, Francesca; Schwab, Annemarie; Natesan, Ramakrishnan; Mielenz, Dirk; Asangani, Irfan Ahmed; Brabletz, Thomas; Pilarsky, Christian; et al. (Oncogene, 2021)
Since their discovery, microRNAs (miRNAs) have been widely studied in almost every aspect of biology and medicine, leading to the identification of important gene regulation circuits and cellular mechanisms. However, investigations are generally focused on the analysis of their downstream targets and biological functions in overexpression and knockdown approaches, while miRNAs endogenous levels and activity remain poorly understood. Here, we used the cellular plasticity-regulating process of epithelial-to-mesenchymal transition (EMT) as a model to show the efficacy of a fluorescent sensor to separate cells with distinct EMT signatures, based on miR-200b/c activity. The system was further combined with a CRISPR-Cas9 screening platform to unbiasedly identify miR-200b/c upstream regulating genes. The sensor allows to infer miRNAs fundamental biological properties, as profiling of sorted cells indicated miR-200b/c as a molecular switch between EMT differentiation and proliferation, and suggested a role for metabolic enzymes in miR-200/EMT regulation. Analysis of miRNAs endogenous levels and activity for in vitro and in vivo applications could lead to a better understanding of their biological role in physiology and disease.
CRIS-Team Scopus Importer:2021-03-19

β8 Integrin Mediates Pancreatic Cancer Cell Radiochemoresistance - Jin, Sha; Lee, Wei Chun; Aust, Daniela; Pilarsky, Christian; Cordes, Nils (Molecular Cancer Research, 2019)
Pancreatic ductal adenocarcinoma (PDAC) stroma, composed of extracellular matrix (ECM) proteins, promotes therapy resistance and poor survival rate. Integrin-mediated cell/ECM interactions are well known to control cancer cell survival, proliferation, and therapy resistance. Here, we identified β8 integrin in a high-throughput knockdown screen in three-dimensional (3D), ECM-based cell cultures for novel focal adhesion protein targets as a critical determinant of PDAC cell radiochemoresistance. Intriguingly, β8 integrin localizes with the golgi apparatus perinuclearly in PDAC cells and resection specimen from PDAC patients. Upon radiogenic genotoxic injury, β8 integrin shows a microtubule-dependent perinuclear-to-cytoplasmic shift as well as strong changes in its proteomic interactome regarding the cell functions transport, catalysis, and binding. Parts of this interactome link β8 integrin to autophagy, which is diminished in the absence of β8 integrin. Collectively, our data reveal β8 integrin to critically coregulate PDAC cell radiochemoresistance, intracellular vesicle trafficking, and autophagy upon irradiation. IMPLICATIONS: This study identified β8 integrin as an essential determinant of PDAC cell radiochemosensitivity and as a novel potential cancer target.
CRIS-Team Scopus Importer:2019-10-11